Carbon nanotubes, carbon nanotube dispersion liquid, secondary battery using the same, and method for producing carbon nanotubes
By optimizing the bulk density and Zr content of carbon nanotubes through controlled dry grinding, the dispersibility and conductivity challenges of carbon nanotubes are addressed, resulting in stable, high-concentration dispersions for secondary batteries with enhanced performance.
Patent Information
- Application Number
- JP2024160995
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-20
AI Technical Summary
Carbon nanotubes exhibit high aspect ratios, leading to difficulty in dispersing them uniformly in a medium due to strong physical bonding, which increases viscosity and makes it challenging to achieve stable, highly concentrated dispersions with good fluidity and conductivity for use in secondary batteries.
Adjusting the bulk density and Zr content of carbon nanotubes within specific ranges, combined with controlled dry grinding, to enhance dispersibility and maintain a high aspect ratio, thereby forming a well-developed conductive network in electrode films.
This approach results in carbon nanotube dispersions with excellent fluidity, storage stability, and high dispersibility, enabling secondary batteries with improved output, capacity, and longevity.
Smart Images

Figure 2025010137000001_ABST
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This disclosure relates to carbon nanotubes and methods for making carbon nanotubes. More specifically, the present invention relates to a carbon nanotube dispersion liquid, a carbon nanotube resin composition containing the carbon nanotube dispersion liquid and a binder resin, a composite slurry containing the carbon nanotube dispersion liquid, a binder resin, and an active material, an electrode film formed from the composite slurry, and a secondary battery including the electrode film. [Background technology]
[0002] Carbon nanotubes have a cylindrical graphite layer structure, and are chemically stable and have electrical conductivity and mechanical toughness, and therefore are used in various applications such as electronic materials, structural materials, paints, etc. Specific applications of carbon nanotubes include electronic materials, semiconductor materials, filler materials, short needle probes for microscopes, adsorption materials, filter materials, etc. In particular, electrode materials using carbon nanotubes are expected to be applied to secondary batteries, fuel cells, electric double layer capacitors, etc. because of their excellent electrical conductivity.
[0003] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of mobile phones, there is a demand for secondary batteries with high energy density and higher capacity. Under these circumstances, non-aqueous electrolyte secondary batteries using non-aqueous electrolytes, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.
[0004] The electrodes of the secondary battery are prepared by coating a composite slurry containing a positive electrode active material or a negative electrode active material, a conductive material, a binder resin, and the like on a current collector. Carbon black, graphene, fine carbon materials, and the like are used as conductive agents, but the use of carbon nanotubes, a type of fine carbon fiber, has been considered for the purpose of further improving the conductivity and improving the capacity of the battery. For example, by adding carbon nanotubes to the positive electrode, the conductivity of the electrode film can be improved and the electrode resistance can be reduced. Among them, multi-walled carbon nanotubes with an outer diameter of several nm to several tens of nm are relatively inexpensive and are being put to practical use. When carbon nanotubes with a small average outer diameter and a large fiber length are used, a conductive network can be efficiently formed even in a small amount, and the capacity of the secondary battery can be increased. On the other hand, carbon nanotubes with these characteristics have a strong cohesive force, making it difficult to further improve the dispersibility of the carbon nanotube dispersion.
[0005] Patent Document 1 proposes to provide a high-concentration, low-viscosity carbon nanotube dispersion containing 2% by mass or more of carbon nanotubes by specifying a wettability index, which is the mass of the absorbed solvent relative to the mass of the carbon nanotubes. In Patent Document 1, the wettability index is controlled by dry-pulverizing the carbon nanotubes using a milling device containing metal or ceramic balls, and in a specific example, batch-type dry pulverization is performed for 10 to 140 minutes using an attrition mill. In addition, Patent Document 2 proposes to provide a carbon nanotube paint that imparts jet blackness and gloss to resin molded bodies, automobile bodies, and the like, by using carbon nanotubes with a specified average outer diameter and surface oxygen concentration. In Patent Document 2, the surface oxygen concentration of the carbon nanotubes is controlled by pulverizing untreated carbon nanotubes using a pulverization medium without the interposition of a liquid medium.
[0006] Patent Document 3 discloses a conductive material dispersion containing a dispersant containing a specific copolymer, a conductive material, and a dispersion medium. Patent Document 3 proposes to provide a conductive material dispersion in which even high-concentration carbon fibers are well dispersed in a dispersion medium by appropriately controlling the dispersion state so that the phase angle at a frequency of 1 Hz in dynamic viscoelasticity measurement of the conductive material dispersion falls within a predetermined range. Patent Document 4 discloses a conductive material dispersion containing a conductive material, a dispersant, and an amide-based organic solvent. Patent Document 4 proposes to provide a conductive material dispersion that can achieve good dispersibility, stability, and handleability by appropriately controlling the dispersion state so that the pH of the conductive material dispersion, and the phase angle and complex modulus at a frequency of 1 Hz in dynamic viscoelasticity measurement fall within a predetermined range. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent No. 10-2125933 [Patent Document 2] JP 2020-029372 A [Patent Document 3] JP 2022-042689 A [Patent Document 4] JP 2022-042691 A Summary of the Invention [Problem to be solved by the invention]
[0008] When carbon nanotubes are dispersed in a dispersion medium, the carbon nanotubes have a high aspect ratio and are strongly physically bonded to each other by van der Waals forces, which makes it difficult for them to spread in the dispersion medium due to the difficulty in untangling the carbon nanotubes and disentangling the bundles. In addition, since dispersing carbon nanotubes in a dispersion medium increases the viscosity of the dispersion, it is difficult to obtain a dispersion containing uniformly dispersed high-concentration carbon nanotubes, and in particular, it is extremely difficult to obtain a high-concentration dispersion that is compatible with fluidity and storage stability. In order to solve the difficulty in dispersion due to the high aspect ratio inherent to carbon nanotubes, a technology has been disclosed in which carbon nanotubes are dry-processed using a grinding medium as in Patent Document 1 and Patent Document 2, thereby improving the wettability of carbon nanotubes to a solvent and obtaining a carbon nanotube dispersion that is low in viscosity even at a high concentration containing 2 mass% or more of carbon nanotubes. However, there is still room for further study in order to fully form a developed conductive network derived from the high aspect ratio inherent to carbon nanotubes in an electrode film using carbon nanotubes.
[0009] Patent Documents 3 and 4 disclose techniques for dispersing carbon nanotubes, which are conductive materials, at high concentrations by controlling the physical properties of the conductive material dispersion, such as the phase angle and complex modulus, in addition to the composition (dispersant type, etc.) and pH of the conductive material dispersion. However, there is room for further study on the method of processing the carbon nanotubes themselves and the stability of the conductive material dispersion over time.
[0010] That is, the problem to be solved by the present invention is to provide carbon nanotubes having high dispersibility and storage stability, and to provide a composite slurry having excellent fluidity and dispersion stability of a carbon nanotube dispersion liquid and good dispersibility even when mixed with an active material. More specifically, the problem to be solved by the present invention is to provide an electrode film having excellent adhesion to a current collector, and a secondary battery having high output, high capacity, and long life, and an electrode film used therein. [Means for solving the problem]
[0011] In order to achieve both the fluidity and storage stability of a dispersion containing carbon nanotubes, it is important to eliminate the high aspect ratio of carbon nanotubes and improve the wettability of carbon nanotubes. On the other hand, in order to fully form a developed conductive network in an electrode film using carbon nanotubes, it is important to disperse the carbon nanotubes while maintaining the high aspect ratio specific to the carbon nanotubes at a certain level or higher, and there is a trade-off between the fluidity, storage stability, and conductivity of the dispersion. According to the inventors' intensive study aimed at solving the above problem, it was found that by setting the bulk density of the carbon nanotubes and the Zr content contained in the carbon nanotubes to appropriate ranges, respectively, it is possible to sufficiently form a conductive network when a conductive film is formed while maintaining the wettability of the CNT to the dispersion medium. In addition, it was found that it is possible to simultaneously achieve the fluidity, storage stability, and conductivity of the dispersion containing the obtained CNT by performing dry processing while carefully controlling the grinding conditions so that both the bulk density of the carbon nanotubes and the Zr content contained in the carbon nanotubes are within appropriate ranges.
[0012] By using the carbon nanotubes according to some embodiments of the present invention, it is possible to provide a carbon nanotube dispersion liquid, a carbon nanotube resin composition, and a composite material slurry that have both flowability and storage stability. Furthermore, by using a composition with good dispersibility of the carbon nanotubes, it is possible to obtain an electrode film having a developed conductive network, and further to provide a secondary battery with high output, high capacity, and long life.
[0013] In addition, the carbon nanotubes according to some embodiments of the present invention have high dispersibility, and therefore can maintain fluidity and storage stability even when a dispersion containing high concentrations of carbon nanotubes is prepared. This allows the carbon nanotubes to be contained uniformly at high concentrations in the electrode film and secondary battery, thereby providing a secondary battery with higher output and capacity.
[0014] That is, the present invention includes the following embodiments, but the embodiments of the present invention are not limited to the following. [1] Bulk density X is 0.095 g / cm 3 More than 0.125g / cm 3 The following carbon nanotubes have a Zr content of 5 ppm or more and 500 ppm or less, and a maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) of 8.0 or more: Y = W / V (5) (In formula (5), V is the mass (g) of the carbon nanotube, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotube when N-methyl-2-pyrrolidone is dropped onto a carbon nanotube of V(g) in a 25°C environment.)
[0015] [2] Bulk density X (g / cm 3 ) and the maximum solvent absorption capacity Y of the carbon nanotube satisfies all of the following formulas (1) to (4): Y≦-200X+37...Equation (1) Y≧200X-17...Equation (2) Y≧-200X+27...Equation (3) Y≦200X+7...Equation (4)
[0016] [3] The carbon nanotube according to [1] or [2], having an average fiber length of 0.2 μm or more and 1.1 μm or less. [4] The carbon nanotubes according to [1] or [2], having an average fiber length of 0.2 μm or more and 1.0 μm or less and a Zr content of 15 ppm or more and 200 ppm or less.
[0017] [5] A carbon nanotube dispersion liquid comprising the carbon nanotubes according to any one of [1] to [4] above, a dispersant, and a non-aqueous dispersion medium. [6] The coefficient of determination R of the regression line represented by the following formula (I) 2 The carbon nanotube dispersion liquid according to [5], wherein the y-intercept b is −5≦b<10 and the y-intercept a is 0.85 or more. y=ax+b Equation (I) (Equation (1) is a regression line obtained by the least squares method from a scatter diagram plotting x on the horizontal axis and y on the vertical axis, measured using carbon nanotube dispersions stored at 40°C for 1 day, 40°C for 7 days, and 40°C for 14 days, respectively.) The number of days elapsed by static storage is i, the static storage temperature is 40°C, and the shear rate is 1.0 s -1 The shear viscosity at η i (Pa s), the complex modulus of elasticity at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is G * i When (Pa) is used, x is 25°C, shear rate 1.0 s -1 The shear viscosity η i (Pa s) natural logarithm (ln(η i )) y is the complex elastic modulus G at 25°C and a frequency of 1 Hz. * i (Pa), i is 1, 7, and 14, with the date of manufacture of the carbon nanotube dispersion being day 0.
[0018] [7] A carbon nanotube resin composition comprising the carbon nanotube dispersion liquid according to [5] or [6] above and a binder resin. [8] A composite slurry comprising the carbon nanotube dispersion liquid according to any one of [5] to [7] above, a binder resin, and an active material. [9] An electrode film formed from the composite slurry described in [8] above.
[10] A secondary battery comprising a positive electrode and a negative electrode, at least one of the positive electrode and the negative electrode having the electrode film according to [9].
[0019]
[11] A method for producing a carbon nanotube having a bulk density X of 0.095 g / cm3, comprising the steps of: dry-pulverizing carbon nanotubes using a milling device including a grinding medium made of a metal or ceramic material; and wherein the dry-pulverization is a pass-type grinding or a circulation-type grinding. 3More than 0.125g / cm 3 The following is a method for producing carbon nanotubes, wherein the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) is 8.0 or more. Y = W / V (5) (In formula (5), V is the mass (g) of the carbon nanotube, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotube when N-methyl-2-pyrrolidone is dropped onto a carbon nanotube of V(g) in a 25°C environment.)
[12] The method for producing carbon nanotubes according to
[11] , wherein a rate of change between bulk density X after dry-milling and bulk density X' before dry-milling is -60% or more and 1000% or less. Bulk density change rate (%) = (X / X'-1) x 100
[13] The method for producing carbon nanotubes according to
[11] or
[12] , wherein the rate of change between the powder resistivity Re after dry grinding and the powder resistivity Re' before dry grinding is 1% or more and 20% or less. Powder resistance change rate (%) = (Re / Re'-1) x 100
[14] The method for producing carbon nanotubes according to any one of
[11] to
[13] , wherein the grinding media are zirconia beads, and the bead diameter of the zirconia beads is greater than 5 mm and less than 10 mm.
[15] The method for producing carbon nanotubes according to any one of
[11] to
[14] , wherein the carbon nanotubes after the dry grinding have an average fiber length of 0.2 μm or more and 1.1 μm or less.
[16] The method for producing carbon nanotubes according to any one of
[11] to
[15] , wherein the carbon nanotubes after the dry grinding have an average fiber length of 0.2 μm or more and 1.0 μm or less and a Zr content of 15 ppm or more and 200 ppm or less.
[17] A method for producing a carbon nanotube dispersion liquid, comprising the steps of mixing and dispersing the carbon nanotubes according to any one of
[11] to
[16] above, a dispersant, and a non-aqueous dispersion medium. Effect of the Invention
[0020] According to an embodiment of the present invention, it is possible to provide carbon nanotubes that exhibit excellent dispersibility, and by using the carbon nanotubes, it is possible to provide a carbon nanotube dispersion liquid that has excellent fluidity and high dispersion stability and storage stability. According to another embodiment of the present invention, it is possible to provide a carbon nanotube resin composition that exhibits excellent fluidity and storage stability even when mixed with a binder resin, and it is possible to provide a secondary battery electrode composite slurry that is unlikely to generate carbon nanotube aggregates or precipitates and can exhibit high conductivity during electrode film formation because the carbon nanotubes have excellent dispersibility even after being mixed with an active material. According to yet another embodiment of the present invention, it is possible to provide a secondary battery with high output, high capacity, and long life. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 shows an example of a scatter plot in which the natural logarithm (ln(η)) of shear viscosity η (Pa s) and complex elastic modulus G* (Pa) measured using carbon nanotube dispersions of Examples and Comparative Examples, and a regression line expressed from the scatter plot by the least squares method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, the carbon nanotubes, the carbon nanotube dispersion, the carbon nanotube resin composition containing the carbon nanotube dispersion and the binder resin, the composite slurry containing the carbon nanotube dispersion, the binder resin, and the active material, the electrode film formed from the composite slurry, the secondary battery including the electrode film, and the method for producing the carbon nanotubes, which are embodiments of the present invention, will be described in detail. The present invention is not limited to the following embodiments, and the present invention also includes embodiments that are implemented within the scope of the present invention.
[0023] The carbon nanotube dispersion liquid and the carbon nanotube resin composition containing the carbon nanotube dispersion liquid and the binder resin refer to the state before the active material is added. In this respect, the carbon nanotube dispersion liquid and the carbon nanotube resin composition are distinguished from a composite slurry containing an active material. That is, the carbon nanotube dispersion liquid and the carbon nanotube resin composition do not substantially contain an active material. This is a concept excluding a state in which an active material is intentionally added to the carbon nanotube dispersion liquid and the carbon nanotube resin composition, and the active material may be 1 mass % or less, 0.5 mass % or less, or 0.1 mass % or less, or may be 0 mass %, based on the total mass of the carbon nanotube dispersion liquid and the carbon nanotube resin composition.
[0024] In this specification, carbon nanotubes may be referred to as "CNT" and N-methyl-2-pyrrolidone as "NMP." Note that in this specification, carbon nanotube dispersions may be referred to as "CNT dispersions" or simply "dispersions."
[0025] <<Carbon nanotubes>> The carbon nanotube of this embodiment has a bulk density X of 0.045 g / cm 3 More than 0.125g / cm 3 The following conditions are met, and the Zr content is 3 ppm or more and 500 ppm or less. This results in carbon nanotubes with excellent dispersibility, and a carbon nanotube dispersion using the carbon nanotubes can achieve both flowability and storage stability. More preferably, the carbon nanotubes have a bulk density X of 0.095 g / cm 3 More than 0.125g / cm 3 It is preferable that the following conditions are satisfied, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the formula (5) described below is 8.0 or more. This makes it possible to further improve the filterability and acid stability of the carbon nanotube dispersion produced using the carbon nanotubes. From another perspective, carbon nanotubes have a bulk density X of 0.045 g / cm 3 More than 0.125g / cm 3 The following conditions are satisfied, the Zr content is 3 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotube defined by the formula (5) described later is 14.0 or more. This allows the CNT dispersion to have dispersibility, and the battery performance in the secondary battery can be improved by the conductive network. In this case, the average fiber length of the CNT is preferably 1.0 μm or more, 1.5 μm or more, or 1.9 μm or more, and preferably 10 μm or less, 5 μm or less, or 2.0 μm or less. Within these ranges, the conductivity and adhesion in the secondary battery can be improved by the conductive network.
[0026] The filterability of the CNT dispersion tends to decrease due to a small amount of aggregates derived from CNTs and other resin components in the CNT dispersion. Therefore, increasing the filterability can improve the degree of CNT disentanglement. This allows the conductive network to be developed further in the secondary battery. In addition, increasing the filterability also has the effect of reducing clogging of filters in the manufacturing processes of the CNT dispersion, the CNT resin composition, and the composite slurry. Regarding the acid stability of the CNT dispersion, if the stability of the CNT dispersion is good even when an acid is added, the viscosity tends to remain good even after aging. One of the reasons for this is thought to be that the acid acts on the CNTs that do not have a dispersant adsorbed thereon, causing aggregation. For this reason, if the acid stability is improved, the stability of the CNT dispersion over time can also be improved. This allows the conductive network to be developed further in the secondary battery.
[0027] The bulk density X of the CNTs contributes to the wettability of the liquid medium, and can also be used as an index of the degree of processing of the CNTs when the CNTs are processed by dry grinding or the like.
[0028] In particular, when using CNTs as a conductive material in battery applications, one of the most important factors is to utilize the high aspect ratio specific to CNTs in the CNT dispersion. When improving the wettability of CNTs in liquid media by dry processing or the like, if the processing intensity is too high, the formation of CNT aggregates is promoted, and as a result, the CNTs cannot be fully dissolved in non-aqueous solvents, and the aspect ratio decreases, which may result in a decrease in conductivity. In addition, it is possible to disperse the CNT aggregates at high intensity without performing CNT processing such as dry grinding, but the resulting dispersion may have poor storage stability due to breakage of CNT fibers, etc. The bulk density of CNT is 0.045 g / cm 3 More than 0.125g / cm 3 By keeping the content below 100%, it is possible to appropriately control the strength of CNT aggregation, the size of the aggregates, etc. Furthermore, since the CNT fibers can be appropriately dispersed in a non-aqueous solvent without breaking and the required electrical conductivity can be maintained, a well-developed conductive network can be formed in the electrode film by forming the electrode film using this dispersion.
[0029] The bulk density of the CNTs is 0.045 g / cm 3 or more, preferably 0.050 g / cm 3 More preferably, it is 0.080 g / cm 3 That is all. Also, 0.125g / cm 3 or less, preferably 0.125 g / cm 3 More preferably, it is 0.120 g / cm or less. 3 or less, and more preferably 0.110 g / cm 3 or less, and particularly preferably 0.100 g / cm 3 The following is the result. The bulk density X of the CNTs is set to 0.090 g / cm from the viewpoint of further improving filterability by appropriately controlling the strength of the CNT agglomeration and the size of the agglomerates. 3 More preferably, 0.095 g / cm 3 More preferably, 0.097 g / cm 3 More than 0.099g / cm 3or more than 0.100g / cm 3 For example, the bulk density X of the CNT may be 0.090 g / cm 3 More than 0.125g / cm 3 Less than 0.095 g / cm is more preferable. 3 More than 0.120g / cm 3 The following is even more preferable. Within these ranges, the filterability and acid stability of the CNT dispersion can be further improved.
[0030] The bulk density X of CNTs in this disclosure is the loose bulk density when loosely packed. The bulk density X can be calculated by allowing CNTs to freely fall into a top-opening container of a given volume until they overflow, leaving the container to stand, smoothing the CNT powder that has risen on the top surface with a leveling plate, measuring the mass of the CNTs, and dividing the mass of the CNTs by the volume of the container.
[0031] A specific method for measuring bulk density X is, for example, to allow CNT powder to freely fall into a 30 ml stainless steel cylindrical container, and after the raised portion on the top surface of the container is scraped off, the mass of the CNT powder is calculated and divided by the volume of the container to obtain the bulk density X. Agglomerates formed during storage of the CNT powder are broken down, and a sufficient amount of sample for testing is passed through a 0.5 mm sieve to allow the obtained sample to flow freely into the measurement container until it overflows.
[0032] The Zr content in the CNT of this embodiment is 3 ppm or more and 500 ppm or less. It is preferably 400 ppm or less, more preferably 300 ppm or less, and further preferably 200 ppm or less, and is preferably 4 ppm or more, and more preferably 5 ppm or more. The Zr content in the CNT is preferably 5 ppm or more, more preferably 10 ppm or more, even more preferably 15 ppm or more, and may be 20 ppm or more, 30 ppm or more, or 40 ppm or more, from the viewpoint of weakening the van der Waals force between the CNTs and further improving the dispersion stability of the CNTs. For example, the Zr content in the CNT is preferably 5 ppm or more and 500 ppm or less, more preferably 10 ppm or more and 300 ppm or less, and even more preferably 15 ppm or more and 200 ppm or less. In these ranges, the dispersion stability in the CNT dispersion can be further improved, and the battery performance can be further improved.
[0033] The Zr content of the CNTs can be measured by inductively coupled plasma (ICP) optical emission spectrometry.
[0034] In addition, the Zr contained in CNTs, which is detected as zirconium element by ICP emission spectrometry, may be a substance (e.g., grinding media, etc.) used in a pretreatment process such as dry treatment of CNTs, may be from wear of disperser parts, or may be introduced by adding a compound such as zirconia (zirconium oxide) containing zirconium to CNTs. The Zr content of CNTs can be adjusted by adjusting the type of dry grinding media, additives / coating agents, and dry grinding treatment conditions (time, strength, treatment temperature, etc.). In addition, the Zr contained in CNTs can be partially reduced by centrifugation, etc., utilizing the specific gravity difference between CNTs and Zr. In addition, Zr has excellent toughness and heat resistance, and most zirconia exists at a size that cannot be classified with CNTs, so it is difficult to remove all of the Zr that has been mixed in at any manufacturing process from CNT pretreatment to CNT dispersions, CNT resin compositions containing them, composite slurries, and finally secondary batteries. Therefore, it is important to appropriately control the Zr content of CNTs by the above-mentioned method, especially for secondary battery applications. The carbon nanotubes according to some embodiments of the present invention have excellent effects because they are carbon nanotube compositions containing Zr.
[0035] The reason why the dispersibility of CNTs becomes good by setting both the bulk density X and the Zr content within the specified range is not clear, but is presumed to be as follows. It is presumed that the presence of Zr weakens the van der Waals forces between CNTs and enhances the dispersion stability of CNTs. When the Zr content is 3 ppm or more, it is not necessary to apply a strong force to uniformly disperse the CNTs that form bundle structures by van der Waals forces, and an increase in the powder resistivity of CNTs and the volume resistivity of an electrode containing CNTs can be suppressed. In addition, when the Zr content is 500 ppm or less, the adsorption of the dispersant to the CNTs is prevented by the excessive Zr contained therein, resulting in an unstable dispersion state, and a decrease in discharge capacity due to Zr adhering to the active material can also be suppressed. More preferably, the Zr content is 5 ppm or more and 500 ppm or less. On the other hand, as mentioned above, the bulk density contributes to the wettability of the liquid medium to the carbon nanotubes, and by appropriately controlling the bulk density, it is possible to disperse the CNTs uniformly and well while maintaining their length at a certain level or higher, and form a well-developed conductive network. By keeping both the bulk density and the Zr content within the specified ranges, it is possible to maximize the electrical conductivity inherent to CNTs while achieving both the dispersibility and stability over time of CNTs.
[0036] The CNT of this embodiment further has a bulk density X (g / cm) from the viewpoint of more finely controlling the defibrillation state of the CNT and microscopically controlling the dispersibility in the CNT dispersion liquid. 3 ) and the maximum solvent absorption capacity Y of the carbon nanotube defined by the following formula (5) preferably satisfies all of the following formulas (1) to (4). Y≦-200X+37...Equation (1) Y≧200X-17...Formula (2) Y≧-200X+27...Equation (3) Y≦200X+7...Equation (4) Y = W / V (5) (In formula (5), V is the mass (g) of the carbon nanotube, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotube when N-methyl-2-pyrrolidone is dropped onto a carbon nanotube of V(g) in a 25°C environment.)
[0037] The maximum solvent absorption capacity Y of CNT is defined by the above formula (5). The maximum solvent absorption capacity Y is the maximum mass of N-methyl-2-pyrrolidone absorbed by CNT per mass of CNT when CNT absorbs N-methyl-2-pyrrolidone. The maximum mass of N-methyl-2-pyrrolidone absorbed by CNT is the total mass of N-methyl-2-pyrrolidone dripped onto CNT powder until just before N-methyl-2-pyrrolidone starts to flow out of the CNT powder.
[0038] Specifically, in a 25°C environment, 5 g (V(g)) of CNT powder is placed in a cylindrical polypropylene container with a diameter of 10 mm by gravity, and while the container is left stationary, 0.5 g of N-methyl-2-pyrrolidone is dropped onto the surface of the CNT powder at intervals of 1 minute. It is observed whether the droplets of N-methyl-2-pyrrolidone begin to flow onto the surface of the CNT powder without being absorbed by the CNT powder. The total mass (g) of N-methyl-2-pyrrolidone dropped until the droplets of N-methyl-2-pyrrolidone begin to flow onto the surface of the CNT powder is defined as W(g).
[0039] The formulas (1) to (4) are explained below. When the maximum solvent absorption capacity Y and the bulk density X obtained above are within the ranges specified by the formulas (1) to (4), the dispersibility and storage stability of the CNTs can be further improved.
[0040] The maximum solvent absorption capacity Y is the maximum mass of N-methyl-2-pyrrolidone absorbed by CNT, but is not limited to the type of dispersion medium. The smaller the maximum solvent absorption capacity, the more likely it is to suppress the increase in the initial viscosity of CNT in the dispersion medium, contributing to improved dispersibility. On the other hand, the bulk density X is a factor that affects the dispersibility and storage stability of CNT in the dispersion medium. Although it cannot be said in general, if the bulk density is large, the sedimentation of CNT in the dispersion medium is more likely to occur, and if the bulk density is small, the wettability of CNT in the dispersion medium decreases, making it easier for dispersibility to decrease.
[0041] Focusing on the fact that the maximum solvent absorption capacity Y and the bulk density X interact with each other to affect the dispersibility and storage stability of carbon nanotubes in a dispersion medium, carbon nanotubes can be specified by the above formulas (1) to (4). When improving the dispersibility and storage stability of carbon nanotubes, it is more preferable to defibrate the carbon nanotubes while maintaining a high aspect ratio, and finely disperse them in the dispersion medium.
[0042] When the maximum solvent absorption capacity Y and the bulk density X do not satisfy the formula (1), that is, when Y>-200X+37, the powder resistivity and the electrode resistivity of the CNTs increase, and the battery performance may deteriorate. Preferably, Y≦-200X+35, and more preferably, Y≦-200X+33.
[0043] When the maximum solvent absorption capacity Y and the bulk density X do not satisfy the formula (2), i.e., when Y<200X-17, aggregation or precipitation of CNTs occurs, the electrode resistivity increases, and the battery performance may deteriorate. Preferably, Y≧200X-13, and more preferably, Y≧200X-9.
[0044] When the maximum solvent absorption capacity Y and the bulk density X do not satisfy the formula (3), that is, when Y<-200X+27, the dispersibility of the CNTs is poor, aggregation and precipitation occur, and the battery performance may be deteriorated. Preferably, Y≧-200X+29, and more preferably, Y≧-200X+31.
[0045] When the maximum solvent absorption capacity Y and the bulk density X do not satisfy the formula (4), i.e., when Y>200X+7, the dispersibility of CNTs is poor, the fluidity and storage stability of the CNT dispersion are reduced, and the battery performance may be reduced. Preferably, Y≦200X+3, more preferably, Y≦200X-1.
[0046] There is no particular limitation on the numerical range of the maximum solvent absorption capacity Y. For example, the maximum solvent absorption capacity may be 5 to 22, 5 to 18, or 14 to 18. In other examples, the maximum solvent absorption capacity may be 5 to 12, or 14 to 22. From the viewpoint of further improving the filterability and acid stability of the CNT dispersion, the maximum solvent absorption capacity Y is preferably 8.0 or more. More preferably, it is 8.4 or more, even more preferably 8.5 or more, and even more preferably 11.8 or more. For example, the maximum solvent absorption capacity Y may be 8.4 or more and 22 or less, 8.5 or more and 18 or less, or 11.8 or more and 12.7 or less. From another viewpoint, the maximum solvent absorption capacity Y is preferably equal to or greater than 14. For example, it may be equal to or greater than 14 and equal to or less than 22, equal to or greater than 16 and equal to or less than 18, or equal to or greater than 17.1 and equal to or less than 17.5. Within these ranges, the dispersion stability of the CNT dispersion can be further increased, and the battery performance can be further improved.
[0047] CNTs include single-walled CNTs and multi-walled CNTs, and may be a mixture of these. Single-walled CNTs have a structure in which one layer of graphite is wound, and multi-walled CNTs have a structure in which two or more layers of graphite are wound. In addition, the sidewalls of CNTs do not have to have a graphite structure. For example, CNTs having sidewalls with an amorphous structure are also CNTs in this specification. The CNTs may be CNTs produced by any method. CNTs can generally be produced by, but are not limited to, laser ablation, arc discharge, thermal CVD, plasma CVD, and combustion methods. The CNTs may also be CNTs that have been surface-treated. The CNTs may be CNT derivatives to which functional groups, such as carboxyl groups, have been added. CNTs that encapsulate organic compounds, metal atoms, or substances, such as fullerenes, may also be used.
[0048] The average outer diameter of the CNTs is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more. Also, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 15 nm or less. The average outer diameter of the CNTs can be calculated by first observing and photographing the CNTs with a transmission electron microscope, randomly selecting 300 CNTs from the observation photograph, and measuring the outer diameter of each of them.
[0049] The average fiber length of the CNTs is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.5 μm or more. Also, it is preferably 5.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. The average fiber length of the CNTs can be calculated by first observing and photographing the CNTs with a scanning electron microscope, randomly selecting 300 CNTs from the observation photograph, and measuring the fiber length of each of them. From the viewpoint of further improving the battery performance by the conductive network of the secondary battery, the average fiber length of the CNT is more preferably 0.2 μm or more, even more preferably 0.5 μm or more, and even more preferably 0.8 μm or more. From the viewpoint of further improving the filterability and acid stability in the CNT dispersion, the average fiber length of the CNT is more preferably 1.5 μm or less, even more preferably 1.1 μm or less, and even more preferably 1.0 μm or less. For example, it may be 0.2 μm or more and 1.5 μm or less, 0.5 μm or more and 1.1 μm or less, or 0.8 μm or more and 1.0 μm or less, more preferably 0.2 μm or more and 1.1 μm or less, and even more preferably 0.2 μm or more and 1.0 μm or less.
[0050] The aspect ratio is the value obtained by dividing the fiber length of the CNT by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. The higher the aspect ratio of the conductive material, the higher the conductivity that can be obtained when an electrode is formed. The aspect ratio of the CNT is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.
[0051] The specific surface area of CNT is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 / g or more is more preferable. 2 / g or less, and 2 / g or less is more preferable, and 2 / g or less is more preferable. The specific surface area of the CNT is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area are within the above ranges, a well-developed conductive path is easily formed in the electrode.
[0052] The carbon purity of CNT is expressed as the content (mass%) of carbon atoms in CNT. The carbon purity is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably 98 mass% or more, relative to 100 mass% of CNT. By keeping the carbon purity within the above range, it is possible to prevent problems such as short circuits caused by the formation of dendrites due to impurities such as metal catalysts. CNTs that have been subjected to a purification treatment for the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity may be used. The method of the purification treatment is not particularly limited, and any known method may be used. CNTs according to some embodiments have a bulk density X of 0.095 g / cm 3 More than 0.125g / cm 3It is preferable that the following conditions are met, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the formula (5) described later is 8.0 or more, and the following conditions (1) or (2) are met. This makes it possible to further improve the filterability and acid stability of the carbon nanotube dispersion produced using the carbon nanotubes. (1) The average fiber length is 0.2 μm or more and 1.1 μm or less. (2) The average fiber length is 0.2 μm or more and 1.0 μm or less, and the Zr content is 15 ppm or more and 200 ppm or less.
[0053] <Method of manufacturing carbon nanotubes> The CNT of the present embodiment is not limited to the manufacturing method, and can be specified by its physical property values. It can be prepared by pretreating CNT manufactured according to a normal manufacturing method or conventionally known CNT. The pretreatment method of CNT is not particularly limited, and may be surface treatment using a chemical, heat treatment, or the like, and one or more pretreatment methods may be used in combination, but it is preferable to at least perform a pulverization treatment. The physical properties of the carbon nanotubes can be controlled by optimizing the pulverization treatment conditions.
[0054] For example, the CNT of this embodiment can be obtained by pulverizing CNTs having easily available physical properties. The pulverization may be either wet pulverization or dry pulverization, and pulverization media may be used. In view of the ease of controlling the physical properties of CNTs, dry pulverization is preferred, and dry pulverization using pulverization media is more preferred. The pulverization media may be made of metal or ceramic material, and is not particularly limited. The components fed into the pulverizer may be only untreated CNTs, but may also contain optional components such as lubricants, dispersants, surface treatment agents, etc. Dry pulverization is preferred, but a liquid medium may be fed into the pulverizer together with the untreated CNTs if necessary.
[0055] When a pulverizer is used, the pulverization process may be performed by any of the batch, pass, and circulation methods, but the pass or circulation method is preferable because of the ease of controlling the physical properties of CNTs, and the circulation method is more preferable. The batch method is a method in which the process is performed only by the dispersion device body without using piping or the like. The pass method is a method in which the pulverizer body is equipped with a tank that supplies CNTs through piping and a tank that receives CNTs, and the CNTs are passed through the pulverizer body. The circulation method is a method in which the CNTs that have passed through the dispersion device body are returned to the tank that supplies CNTs and processed while circulating. In either case, the longer the processing time, the more the pulverization process progresses, so it is sufficient to repeat the pass or circulation until the desired state is reached, and the processing amount can be increased by changing the size of the tank and the processing time. Specific examples of pulverizers include a bead mill, a ball mill, and an attrition mill, but the ball mill and the attrition mill fall under the batch processing category. As a pulverizer of the pass or circulation type, for example, a dry continuous pulverizer equipped with a high-speed rotating arm in a horizontal cylindrical tank and stirring the pulverization media can be used. When zirconia beads are used as the grinding media, it is preferable to use a pass-type or circulation-type dry continuous grinding device from the viewpoint of adjusting the Zr content of the CNTs to an appropriate range.
[0056] In the pass-type or circulation-type grinding process, the desired CNTs can be obtained by controlling the input mass per unit time of the CNTs input into the grinding device, the type of grinding media, the diameter, the input amount, the grinding temperature, etc. In one example, it is good to input the CNT raw material using a circulation-type bead mill and perform dry grinding. Methods for controlling the grinding temperature include a method of cooling with a cooling jacket provided in the grinding chamber body, a method of cooling outside the bead mill system, and a method of cooling using both of these. From the viewpoint of cooling efficiency, the method of cooling with a cooling jacket provided in the grinding chamber body is preferable. In addition, the grinding temperature can be measured by installing a thermometer in any pipe, and specifically, it can be confirmed by the powder outlet temperature measured by installing a thermometer at the outlet of the bead mill.
[0057] When dry grinding is performed using grinding media, the grinding media is preferably made of ceramic material, and zirconia is more preferable, in order to prevent metal impurities such as iron from being mixed into the CNTs and to improve the grinding strength. The grinding media diameter is preferably 1 mm or more, more preferably 3 mm or more, and even more preferably 5 mm or more. By having the grinding media diameter be greater than the above range, the collision energy to the CNTs is increased, and the dry grinding efficiency can be improved. In addition, the grinding media diameter is preferably 15 mm or less, more preferably 10 mm or less, and even more preferably 8 mm or less. By having the grinding media diameter be less than the above range, wear due to collision between the grinding media can be reduced. In addition, the grinding media used in dry grinding of CNTs can wear or crack due to repeated use, which can cause poor dispersion processing or contamination. Therefore, it is preferable to classify and wash the grinding media before use. When using zirconia beads as the grinding media, the bead diameter is preferably more than 5 mm and less than 10 mm from the viewpoint of more appropriately adjusting the Zr content of the CNT. When two or more types of beads with significantly different diameters are used in combination, the beads are worn due to collisions with each other, and a large amount of Zr is likely to be mixed into the CNT, so the bead diameter should be within ±1 mm. This tendency is stronger in a bead mill for dry grinding, so when using a bead mill, it is preferable to use one type of zirconia beads, and it is more preferable to set the bead diameter of the zirconia beads to ±1 mm.
[0058] Here, the necessity and effects of pretreatment of CNTs, particularly dry treatment, will be described in detail. If a CNT dispersion is prepared while the CNTs maintain their length, i.e., while maintaining a high aspect ratio, the bulkiness of the CNTs causes poor wettability to the dispersion medium, which may lead to poor handling, an increase in the viscosity of the dispersion, and a decrease in uniformity. In addition, the composite slurry produced using such a CNT dispersion also becomes highly viscous and non-uniform, which may lead to a decrease in the coatability of the electrode film and a decrease in the uniformity of the electrode film. On the other hand, if the bulk density becomes too large due to pretreatment, the preparation of the CNT dispersion (specifically, the ease of loading and wettability to the dispersion medium, etc.) becomes easier and the finished viscosity of the dispersion tends to be lower, but the specific surface area of the CNTs increases, and a large amount of dispersant is required to obtain sufficient stability, which is undesirable from the viewpoint of designing the electrode film. In addition, CNTs in an aggregated state with a high bulk density, or CNTs that are dispersed with high strength and broken short to break the aggregates, are difficult to form a developed conductive network, and there is a risk of the conductivity being deteriorated. Furthermore, if the viscosity of the composite slurry becomes too low, migration may occur during the drying process when preparing the electrode film, which may cause the electrode film to become uneven. Furthermore, if the CNTs are pretreated to the extent that the bulk density becomes too high, there is a risk that Zr may inhibit the adsorption of the dispersant to the CNTs, and there is also a concern that Zr may adhere to the active material, causing a decrease in discharge capacity. In view of these, by obtaining CNTs with both the bulk density and Zr content appropriately controlled, it is possible to realize a CNT dispersion liquid with excellent dispersibility, stability, and conductivity; furthermore, it is possible to obtain an electrode film with a well-developed conductive network, and further to provide a secondary battery with high output, high capacity, and long life.
[0059] The bulk density X of the CNT is 0.045 g / cm 3 ~0.125g / cm 3 and the Zr content of the CNTs is adjusted to a range of 3 ppm to 500 ppm, thereby making it possible to obtain CNTs with excellent performance. More preferably, the bulk density X of the CNTs is adjusted to 0.095 g / cm 3 ~0.125g / cm 3 It is preferable to adjust the Zr content of the CNT to within a range of 5 ppm to 500 ppm, and adjust the maximum solvent absorption capacity Y to 8.0 or more.
[0060] Furthermore, the present inventors have found that when dry treatment is used as a pretreatment of CNTs, it is necessary to improve the wettability to a certain level while maintaining a high aspect ratio of the CNTs to a certain extent. Therefore, the inventors have found that by setting the bulk density X of the CNTs and the Zr content of the CNTs within the above ranges as indicators for determining the degree of CNT treatment, in other words, the end point of the dry treatment of CNTs, CNTs with excellent dispersibility and electrical conductivity can be obtained.
[0061] That is, when dry processing is adopted as the pretreatment of CNT, it is performed while controlling the bulk density X of CNT and the Zr content of CNT. It is preferable to appropriately adjust the dry processing conditions of CNT by evaluating the dispersibility of the CNT dispersion liquid, the composite slurry using it, and even the conductivity of the electrode film, but for the above reasons, the bulk density X and the Zr content may be measured during the dry processing, and these physical properties may be directly used as indicators for obtaining a desired processing state.
[0062] The rate of change between the bulk density X after dry grinding and the bulk density X' before dry grinding is preferably -60% or more and 1000% or less, more preferably -20% or more and 500% or less, and even more preferably -5% or more and 250% or less. By keeping the rate of change in bulk density within the above range, it is possible to obtain CNTs that exhibit better dispersibility and high electrical conductivity. The bulk density change rate is calculated by the following formula. Bulk density change rate (%) = (X / X'-1) x 100
[0063] The rate of change between the powder resistivity Re after dry grinding and the powder resistivity Re' before dry grinding is preferably 1% to 20%, more preferably 2% to 18%, and even more preferably 3% to 15%. By keeping the rate of change in powder resistivity within the above range, CNTs exhibiting better dispersibility and high electrical conductivity can be obtained. The rate of change in powder resistance value is calculated by the following formula. Powder resistance change rate (%) = (Re / Re'-1) x 100
[0064] The average fiber length of the CNTs after dry pulverization is preferably 0.1 μm or more and 5 μm or less, may be 0.2 μm or more and 2 μm or less, or may be 0.5 μm or more and 1 μm or less. When the fiber length of the carbon nanotubes is 0.1 μm or more, the electrical conductivity and toughness can be further increased. In addition, when the fiber length of the carbon nanotubes is 1 μm or less, even if defibration progresses in the dispersion treatment of the CNTs in a non-aqueous dispersion medium, the occurrence of aggregation can be suppressed, and the viscosity increase of the dispersion can be further prevented. In addition, the average fiber length of the CNTs before dry pulverization is not particularly limited, but it is preferably 0.6 μm or more, more preferably 0.9 μm or more, and even more preferably 1.2 μm or more, because it is preferable to appropriately control the fiber length distribution of the CNTs by performing the dry pulverization treatment. In addition, it is preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less. The average fiber length of the CNTs can be calculated by the above-mentioned method. In addition, since it is preferable to appropriately adjust the dry processing conditions, etc. depending on the average outer diameter and average fiber length of the CNTs before dry processing, the rate of change between the average fiber length of the CNTs after dry grinding and the average fiber length of the CNTs before dry grinding is not particularly limited.
[0065] The untreated CNTs are not particularly limited, and may be CNTs produced by any method. CNTs can generally be produced by, but are not limited to, laser ablation, arc discharge, thermal CVD, plasma CVD and combustion. For example, CNTs can be produced by contacting a carbon source with a catalyst at 500 to 1000°C in an atmosphere with an oxygen concentration of 1% by volume or less. Any conventionally known raw material gas can be used as the carbon source for untreated CNTs. For example, as a raw material gas containing carbon, hydrocarbons such as methane, ethylene, propane, butane and acetylene, carbon monoxide and alcohols can be used, but are not limited to these. In particular, from the viewpoint of ease of use, it is desirable to use at least one of hydrocarbons and alcohols as the raw material gas.
[0066] Furthermore, untreated CNTs usually exist as secondary particles. The shape of these secondary particles may be, for example, a state in which CNTs, which are general primary particles, are intricately entangled. They may also be an aggregate of linear CNTs. Secondary particles that are an aggregate of linear CNTs are easier to disentangle than entangled ones. Furthermore, linear ones have better dispersibility than entangled ones, so they can be suitably used as CNTs. It is preferable to perform a pulverization process on these untreated CNTs so that they satisfy the desired physical property values.
[0067] Furthermore, the untreated CNT may be a surface-treated CNT. The CNT may be a CNT derivative to which a functional group such as a carboxyl group is added. When a pulverization process is performed, the above-mentioned treatments may be performed before, after, or simultaneously with the pulverization process, or a combination of these.
[0068] In addition, the distribution of fiber length, pore size, etc. of untreated CNTs varies depending on the type. Therefore, the compression of CNTs and the way in which CNTs are broken by dry grinding and other processes vary depending on the type of CNT. Since the distribution of various properties of the obtained CNTs varies depending on the type of CNT and the processing method, etc., it is advisable to apply an appropriate processing method depending on the type of CNT. For example, the selection of a grinding processing device and the processing time, etc., may be appropriately adjusted as the processing method.
[0069] <<Carbon nanotube dispersion liquid>> The CNT dispersion of the present embodiment contains the above-mentioned CNTs, a dispersant, and a non-aqueous dispersion medium. Details of the CNTs are as described above.
[0070] <Dispersant> The CNT dispersion contains a dispersant. The dispersant is not particularly limited, but is preferably one that can stabilize the dispersion of CNTs in the CNT dispersion. The dispersant may be either a resin-type dispersant or a surfactant, but a resin-type dispersant is preferred because it has a strong adsorption power to CNTs and provides good dispersion stability. Depending on the characteristics required for dispersing CNTs, a suitable type of dispersant can be used in a suitable amount.
[0071] As the resin-type dispersant, a (meth)acrylic polymer, a polymer derived from an ethylenically unsaturated hydrocarbon, a cellulose derivative, a copolymer thereof, or the like can be used.
[0072] Examples of the polymer derived from an ethylenically unsaturated hydrocarbon include polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylonitrile resins, nitrile rubbers, etc. Examples of the polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohols having functional groups other than hydroxyl groups (e.g., acetyl groups, sulfo groups, carboxy groups, carbonyl groups, amino groups), polyvinyl alcohols modified with various salts, other anion- or cation-modified polyvinyl alcohols, polyvinyl acetals (polyvinyl acetoacetal, polyvinyl butyral, etc.) modified with aldehydes (acetoacetal-modified or butyral-modified, etc.), etc. The polyacrylonitrile resin may be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, or a modified product thereof. A polyacrylonitrile resin having at least one selected from the group consisting of active hydrogen groups such as hydroxyl groups, carboxy groups, primary amino groups, secondary amino groups, and mercapto groups, basic groups, (meth)acrylic acid alkyl esters, or alkyl groups derived from α-olefins, etc. is preferred. For example, the acrylonitrile copolymer described in JP-A-2020-163362 can be used. Examples of nitrile rubbers include acrylonitrile butadiene rubber and hydrogenated acrylonitrile butadiene rubber. Examples of cellulose derivatives include cellulose acetate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, or copolymers thereof. In addition, dispersants described in International Publication No. 2008 / 108360, JP 2018-192379 A, JP 2019-087304 A, JP 2020-011934 A, and JP 2009-026744 A may be used, but are not limited to these.Particularly preferred are methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, homopolymers of polyacrylonitrile, copolymers of polyacrylonitrile, and hydrogenated acrylonitrile butadiene rubber. Polymers in which other substituents have been introduced into a portion of these polymers, modified polymers, etc. may also be used.
[0073] The weight average molecular weight of the resin-type dispersant is preferably 500,000 or less, more preferably 300,000 or less, from the viewpoint of the affinity balance between the CNT to be dispersed and the non-aqueous dispersion medium, and from the viewpoint of resistance to the electrolyte. Also, it is preferably 3,000 or more, more preferably 5,000 or more. The resin-type dispersant may be used alone or in combination of two or more. The weight average molecular weight is the weight average molecular weight in terms of polystyrene obtained by gel permeation chromatography (GPC) measurement.
[0074] Commercially available polyvinyl alcohol resins are available in various grades under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry Co., Ltd.), Denka Poval (polyvinyl alcohol resin manufactured by Denka Co., Ltd.), and J-Poval (polyvinyl alcohol resin manufactured by Nippon Acetate Poval Co., Ltd.). Modified polyvinyl alcohols having various functional groups are also available. Polyvinyl alcohols synthesized by known synthesis methods may also be used. Specific examples of commercially available polyvinylpyrrolidone resins include Luvitec K17 (K value: 15.0 to 19.0, low molecular weight), K30 (K value: 27.0 to 33.0), K90 (K value: 88.0 to 92.0), K90HM (K value: 92.0 to 96.0, high molecular weight) (manufactured by BASF Japan), K15, K30, K90, K120 (manufactured by ISP), polyvinylpyrrolidone K30 (K value: 27.0 to 33.0), K90 (K value: 88.0 to 96.0) (manufactured by Nippon Shokubai), PVP Examples of the polyvinylpyrrolidone include K12 (K value 10-14), K15 (K value 13-19), K30 (K26-K35), K60 (K value 50-62), and K90 (K value 88-100) (manufactured by DSP Gokei Food & Chemical). From the viewpoint of preventing an increase in viscosity, the polyvinylpyrrolidone preferably has a K value of 150 or less, more preferably a K value of 100 or less, and even more preferably a K value of 85 or less. As commercially available nitrile rubbers, various grades with different nitrile ratios, hydrogenation rates, and molecular weights can be obtained under trade names such as Therban (hydrogenated nitrile rubber manufactured by Aranseo), Baymod (nitrile rubber manufactured by Aranseo), Zetpole (hydrogenated nitrile rubber manufactured by Nippon Zeon), and Nipole NBR (nitrile rubber manufactured by Nippon Zeon). Also, those synthesized by a known synthesis method may be used.
[0075] Surfactants may be used in place of or in addition to the resin-type dispersants described above. Surfactants are classified into anionic, cationic, amphoteric ionic surfactants and nonionic surfactants.
[0076] The CNT dispersion may further contain a base. It is preferable that the CNT dispersion contains a base, since it enhances the wettability of the CNTs to the dispersion medium, thereby improving the dispersibility, or improving the dispersion stability. At least one base selected from the group consisting of inorganic bases, inorganic metal salts, organic bases, and organic metal salts can be added. The total amount of these is preferably 0.001 to 0.1 mass %, more preferably 0.005 to 0.05 mass %, based on the total amount of the CNT dispersion. If the amount of base added is too large, it may cause corrosion of the dispersion device and / or the inside of the battery. Here, the water content of the base to be added is preferably less than 5% by mass, more preferably less than 3% by mass, and even more preferably less than 2% by mass. If the base to be added contains a large amount of water, the adsorption of the dispersant to the CNT may decrease, and it may be difficult to make the CNT stably exist in the non-aqueous dispersion medium. By setting the water content within the above range, it is possible to prevent the problem that the composite slurry produced by mixing with the active material gels, or the problem that moisture remains in the positive electrode and the deterioration of the positive electrode occurs due to the generation of an acid such as HF. There is a problem that moisture remains in the positive electrode and the deterioration of the positive electrode occurs due to the generation of an acid such as HF. In addition, if moisture is present in an alkali metal hydroxide such as LiOH, the paste containing the positive electrode active material is likely to gel when the positive electrode is prepared, making it difficult to form the electrode.
[0077] Examples of inorganic bases and inorganic metal salts include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, borates, and ammonium hydroxide of alkali metals or alkaline earth metals. Among these, hydroxides or alkoxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal possessed by the inorganic base may be a transition metal.
[0078] Examples of the organic base include primary, secondary and tertiary amine compounds having 1 to 40 carbon atoms (eg, alkylamines and amino alcohols) which may have a substituent, and organic hydroxides. Examples of the primary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as propylamine, butylamine, isobutylamine, octylamine, 2-ethylhexylamine, and laurylamine; aminoalcohols such as 2-aminoethanol and 3-aminopropanol; and 3-ethoxypropylamine. Examples of the secondary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as dibutylamine, diisobutylamine, N-methylhexylamine, and dioctylamine, and aminoalcohols such as 2-methylaminoethanol. Examples of the tertiary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as triethylamine, tributylamine, N,N-dimethylbutylamine, N,N-diisopropylethylamine, dimethyloctylamine, trioctylamine, and dimethyldecylamine, triethanolamine, and 2-(dimethylamino)ethanol. The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Examples of the organic hydroxide include trimethyl-2-hydroxyethyl ammonium hydroxide, tetramethyl ammonium hydroxide, trimethyl phenyl ammonium hydroxide, 3-trifluoromethyl-phenyl trimethyl ammonium hydroxide, and benzyl trimethyl ammonium hydroxide. Among these, from the viewpoint of the action on CNTs, it is more preferable to use at least one selected from the group consisting of 2-aminoethanol, 3-aminopropanol, triethanolamine, and trimethyl-2-hydroxyethylammonium hydroxide.
[0079] Examples of organic metal salts include alkoxides of alkali metals and acetates of alkali metals. Examples of alkoxides of alkali metals include lithium methoxide, lithium ethoxide, lithium propoxide, lithium t-butoxide, lithium n-butoxide, sodium methoxide, sodium ethoxide, sodium propoxide, sodium t-butoxide, sodium n-butoxide, potassium methoxide, potassium ethoxide, potassium propoxide, potassium t-butoxide, and potassium n-butoxide. Among these, sodium t-butoxide is preferred from the viewpoint of easily supplying cations. The metal contained in the organic base may be a transition metal.
[0080] The CNT dispersion may further contain an acid. It is preferable to contain an acid in the CNT dispersion, since it can suppress the polymerization of the resin and the associated increase in viscosity and gelation of the composite slurry for the lithium ion battery positive electrode. The acid to be added may be either an inorganic acid or an organic acid. The total amount of these is preferably 0.001 to 1.0 mass % relative to the total amount of the CNT dispersion, and more preferably 0.005 to 0.5 mass %. If the amount of acid added is too large, there is a risk of reducing the adsorption and dispersion ability of the dispersant to the CNTs.
[0081] Examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. Examples of organic acids include carboxylic acid compounds and sulfonic acid compounds. Examples of carboxylic acid compounds include formic acid, acetic acid, propionic acid, butyric acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, (meth)acrylic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, citraconic acid, and fluoroacetic acid. Examples of sulfonic acid compounds include methanesulfonic acid, paratoluenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, and dinonylnaphthalenedisulfonic acid. In addition, anhydrides, hydrates, or acids in which a part of the above acids is a salt can also be used. These can be used alone or in combination of two or more.
[0082] <Non-aqueous dispersion medium> The CNT dispersion liquid contains a non-aqueous dispersion medium as a dispersion medium. The non-aqueous dispersion medium is not particularly limited, but is preferably a high-dielectric constant solvent, and preferably contains a solvent consisting of any one of the high-dielectric constant solvents, or a mixed solvent consisting of two or more of them. In addition, the high-dielectric constant solvent may be mixed with one or more other solvents.
[0083] Examples of high dielectric constant solvents include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), and others, such as tetrahydrofuran, urea, and acetonitrile. The relative dielectric constant of the high dielectric constant solvent can be a value described in a solvent handbook, etc., and is preferably 2.5 or more at 20°C.
[0084] From the viewpoint of the solubility of the dispersant or binder resin, or the wettability of the CNTs to the dispersion medium, the non-aqueous dispersion medium preferably contains an amide-based organic solvent, and more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.
[0085] The content of the amide organic solvent is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more, based on the total mass of the non-aqueous dispersion medium. From the viewpoint of handling, it is more preferable to use N-methyl-2-pyrrolidone alone.
[0086] The CNT dispersion may contain optional components such as other additives, such as a wetting agent, a wetting penetrant, a leveling agent, etc., as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the CNT dispersion, during mixing, after mixing, or a combination of these.
[0087] Since the inclusion of optional components does not impair the object of the present invention and the CNT dispersion does not substantially contain active materials, the content of CNTs and dispersant in the CNT dispersion is 60 mass% or more, preferably 70 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and even more preferably 95 mass% or more, based on the non-volatile components of the CNT dispersion, i.e., the solid content of the CNT dispersion, and may be 100 mass% or less.
[0088] As the conductive material other than CNT, carbon black can be included. Carbon black is preferably included in the CNT dispersion liquid within a range that does not impair the effects of the present invention, and the CNT is preferably 1 to 80 mass% and more preferably 1 to 50 mass% based on the total mass of carbon black and CNT. If the above range is satisfied, even if carbon black is included, the dispersion state of CNT can be controlled and high dispersibility and flowability can be maintained better. Furthermore, the carbon black is preferably 20 mass% or less and more preferably 15 mass% or less based on the total mass of the CNT dispersion liquid.
[0089] The step of adding carbon black to the CNT dispersion is not particularly limited and may be before, after, simultaneous with, or a combination of these in relation to the addition of CNT. As another example of a method for producing a CNT dispersion containing carbon black, there is a method of adding carbon black before, after, simultaneous with, or a combination of these in relation to the addition of a binder resin to the CNT dispersion. In this method, it is preferable that carbon black is added in a state where CNT is dispersed in the CNT dispersion. Alternatively, a combination of these methods may be used. That is, carbon black may be further added before, after, simultaneous with, or a combination of these in relation to the addition of a binder resin to the CNT dispersion containing carbon black.
[0090] <Method for producing CNT dispersion> The CNT dispersion of the present embodiment is characterized by comprising a step of mixing and dispersing the above CNT, a dispersant, and a non-aqueous dispersion medium. For example, it is preferable to produce CNT, a dispersant, and a non-aqueous dispersion medium by performing a dispersion treatment using a dispersion device to finely disperse them. The dispersion device used for performing such a treatment is not particularly limited. Note that the dispersion treatment may arbitrarily adjust the addition timing of the materials used and may be a multi-stage treatment of two or more times.
[0091] Examples of the dispersing device used when dispersing CNT include a kneader, a two-roll mill, a three-roll mill, a planetary mixer, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, an attritor, a high shear mixer, a high pressure homogenizer, an ultrasonic homogenizer, and the like. Among them, in order to finely disperse CNT in the CNT dispersion and obtain suitable dispersibility, it is preferable to use a high shear mixer, a high pressure homogenizer, an ultrasonic homogenizer, or a combination of these. In particular, from the viewpoint of promoting wetting of CNT and dissolving coarse particles, it is preferable to use a high shear mixer in the initial dispersion step, and then to use a high pressure homogenizer from the viewpoint of dispersing while maintaining the aspect ratio of CNT. The high pressure homogenizer can further increase the dispersibility of CNT by performing the dispersion in multiple stages by circulation dispersion. In addition, by dispersing with a high pressure homogenizer and then dispersing with a bead mill, the dispersion state can be made uniform while maintaining the fiber length. In some embodiments of the present invention, CNTs with improved wettability due to dry processing or the like are dispersed using a high shear mixer in the initial dispersion step, followed by dispersion in a bead mill and further dispersion in a high-pressure homogenizer, whereby the CNTs aggregated by a certain force due to dry processing or the like can be sufficiently loosened and the dispersion state can be made uniform. When using a high-pressure homogenizer, the pressure in the homogenizing section of the high-pressure homogenizer is preferably 60 to 150 MPa, more preferably 60 to 120 MPa.
[0092] Dispersion methods using a dispersion device include batch dispersion, pass dispersion, circulation dispersion, etc., and any of these methods may be used, or two or more methods may be combined. Batch dispersion is a method in which dispersion is performed using only the dispersion device body without using piping or the like. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersion device body is equipped with a tank that supplies the dispersion liquid through piping and a tank that receives the dispersion liquid, and the dispersion liquid is passed through the dispersion device body. In addition, circulation dispersion is a method in which the dispersion liquid that has passed through the dispersion device body is returned to the tank that supplies the dispersion liquid, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so it is sufficient to repeat the pass or circulation until the desired dispersion state is reached, and the processing amount can be increased by changing the size of the tank or the processing time. Pass dispersion is preferable in that it is easier to uniformize the dispersion state compared to circulation dispersion. Circulation dispersion is preferable in that the work and manufacturing equipment are simple compared to pass dispersion. In the dispersion step, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of the conductive material proceed sequentially or simultaneously, and the final dispersion state differs depending on how the steps proceed, so it is preferable to control the dispersion state in each dispersion step by using various evaluation methods. For example, the dispersion state can be controlled by the method described in the Examples.
[0093] The dispersing device used for dispersing the CNT dispersion may be equipped with a heat exchanger or a cooling liquid supply mechanism for cooling the CNT dispersion. By previously cooling the CNT dispersion or the crude dispersion that has become hot after dispersion, it is possible to suppress the generation of bubbles in the CNT dispersion and also to suppress the remaining solid content on the wall surface of the dispersion tank, etc. The liquid temperature of the CNT dispersion is not particularly limited, but is preferably controlled to 25 to 75°C, and more preferably controlled to 40 to 65°C.
[0094] In the CNT dispersion of the present embodiment, from the viewpoint of microscopically controlling the dispersibility and fluidity of CNTs in the CNT dispersion, the regression line formula (I) is further 2 It is preferable that the y-intercept b satisfies −5≦b<10, the slope a satisfies 2≦a<20, and the y-intercept b satisfies −5≦b<10. y=ax+b...Eq. (I) (Equation (I) is a regression line obtained by the least squares method from a scatter diagram plotting x on the horizontal axis and y on the vertical axis, which is measured using carbon nanotube dispersions with static storage temperatures and days of 40°C for 1 day, 40°C for 7 days, and 40°C for 14 days, respectively. The regression line is obtained by the least squares method from a scatter diagram plotting x on the horizontal axis and y on the vertical axis, which is measured using carbon nanotube dispersions with static storage temperatures and days of 40°C for 1 day, 7 days, and 14 days, respectively, and is a regression line ... -1 The shear viscosity at η i (Pa s), the complex modulus of elasticity at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is G * i (Pa), x is the above shear viscosity η i (Pa s) natural logarithm (ln(η i )) and y is the complex elastic modulus G at 25 ° C. and a frequency of 1 Hz. * i (Pa), and i is 1, 7, and 14, with the production date of the carbon nanotube dispersion being day 0.)
[0095] By satisfying certain conditions in formula (I), the CNT dispersion liquid has excellent dispersion stability of CNTs, and the dispersibility and fluidity of the CNT dispersion liquid are maintained even after aging. Furthermore, by using this CNT dispersion liquid, the dispersibility and fluidity are maintained even after a binder resin is added, and a conductive network developed in the electrode film can be formed when the electrode film is produced. This results in an electrode film with excellent adhesion to the current collector, and a secondary battery with high output, high capacity, and long life can be obtained.
[0096] A CNT dispersion that satisfies the specific conditions in formula (I) can be obtained by appropriately controlling the types and contents of CNTs, dispersants, and non-aqueous dispersion medium, as well as the mixing conditions, dispersion conditions, etc. In particular, it is effective to appropriately control the bulk density of CNTs and the Zr content in CNTs, and for example, using CNTs whose pretreatment conditions have been optimized to satisfy formula (I) can be used as an index for judging a good dispersion state in a CNT dispersion. More specifically, CNTs with a bulk density and Zr content within the appropriate ranges have a good aspect ratio and form an aggregated state, so that when they are dispersed, a CNT dispersion liquid can be obtained in which the CNTs are sufficiently detangled. Also, by not containing excessive Zr, a CNT dispersion liquid with excellent storage stability can be obtained.
[0097] In this way, the dispersibility of CNTs in a CNT dispersion can be evaluated by the shear viscosity and the complex modulus in dynamic viscoelasticity measurements, and by adjusting the CNT pretreatment method so that the shear viscosity and complex modulus of a CNT dispersion under specific conditions satisfy the above relationship, high dispersibility and fluidity can be maintained even in a CNT dispersion containing a high concentration of CNTs. The regression line of the present disclosure can be determined by measurement using a CNT dispersion after static storage at 40°C for 1, 7, and 14 days.
[0098] Coefficient of determination R 2 If the ratio is less than 0.85, CNT aggregates will be present in the CNT dispersion, and aggregation and precipitation of the CNTs will occur over time, which may result in a decrease in the adhesion of the electrode film and a decrease in battery performance. R 2 is preferably 0.90 or more, and more preferably 0.95 or more. Here, the coefficient of determination R 2 can be calculated from the square of the Pearson product-moment correlation coefficient.
[0099] The slope a can be 2≦a<20. If the slope a is less than 2, the CNTs in the CNT dispersion are present in a non-uniform state, which may cause a decrease in the adhesion of the electrode film and a decrease in battery performance. If the slope a is 20 or more, aggregation and precipitation of the CNTs occur in the CNT dispersion, which may cause an increase in electrode resistance and a decrease in battery performance. The slope a is preferably equal to or greater than 2, more preferably equal to or greater than 5, and even more preferably equal to or greater than 7. Moreover, the slope a is preferably less than 20, more preferably less than 15, and even more preferably less than 14.
[0100] The y-intercept b can be -5≦b<10. If the y-intercept b is less than -5, the CNTs in the CNT dispersion are present in a non-uniform state, which may cause a decrease in the adhesion of the electrode film and a decrease in the battery performance. If the y-intercept b is 10 or more, the CNTs may aggregate or settle in the CNT dispersion, which may cause an increase in the electrode resistance and a decrease in the battery performance. The y-intercept b is preferably −5 or more, more preferably −3 or more, and even more preferably greater than 0. In addition, the y-intercept b is preferably less than 10, more preferably less than 8, and even more preferably less than 6.
[0101] By controlling the dispersion state of CNTs and creating a CNT dispersion liquid such that formula (I) satisfies specific conditions, it is possible to simultaneously achieve the dispersion stability, temporal stability, adhesion between the electrode film and the current collector, and battery characteristics of the CNT dispersion liquid.
[0102] The symbol i represents the number of days that have passed since static storage, with the production date of the CNT dispersion being day 0, and is 1, 7, and 14. That is, with formula (I), the shear viscosity and complex modulus are measured using the CNT dispersion after static storage at 40°C for 1, 7, and 14 days from the production date, respectively, and a regression line can be obtained from the three points obtained by plotting x and y.
[0103] x is 25°C, shear rate 1.0 s -1 Shear viscosity η i (Pa s) natural logarithm (ln(η i ) where the shear viscosity η i (Pa s) represents the shear viscosity η (Pa s) measured using the CNT dispersion after storing it at 40°C for i days.
[0104] y is the complex modulus G at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * i (Pa). Here, the complex elastic modulus G * i (Pa) is the complex modulus G measured using a CNT dispersion after storing at 40°C for i days. *(Pa).
[0105] The shear viscosity η (Pa s) of the CNT dispersion was measured at 25°C and a shear rate of 1.0 s -1 The complex modulus G * (Pa) is the measured value at 25°C and a frequency of 1 Hz. For details, it can be measured by the method described in the Examples. The shear rate of a CNT dispersion tends to be smaller as the dispersibility of CNTs improves, but when the fiber length of the CNTs is large, the value itself may be high even if the CNTs are uniformly and stably dissolved in the medium, due to the structural viscosity of the CNTs themselves. In addition to the dispersion state of the CNTs, it also changes due to the entanglement of the CNTs, dispersants, and other resin components, or the influence of their intermolecular forces.
[0106] The complex modulus indicates the hardness of the CNT dispersion, and tends to be smaller the better the dispersibility of the CNTs and the lower the viscosity of the CNT dispersion. However, just like the shear viscosity, if the CNTs themselves have structural viscosity, the CNT dispersion may have a high value even if the CNTs are uniformly and stably dissolved in the medium. In addition to the dispersion state of the CNTs, it also changes due to the entanglement of the CNTs, dispersants, and other resin components, or the influence of their intermolecular forces.
[0107] CNT dispersion temperature 25℃ and shear rate 1.0 s -1 The shear viscosity η (Pa s) in is preferably 0.05 or more, more preferably 0.20 or more, and even more preferably 0.80 or more. When the shear viscosity η is within the above range, the CNTs are sufficiently disintegrated, and a CNT dispersion liquid in which the CNTs are uniformly dispersed can be obtained, resulting in high composite adhesion and excellent battery performance. Moreover, the shear viscosity η is preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.0 or less. By having the shear viscosity η within the above range, a CNT dispersion liquid in which the CNTs are stably dispersed without aggregation or sedimentation of the CNTs can be obtained, and excellent battery performance can be obtained.
[0108] Complex modulus G of CNT dispersion at 25℃ and 1Hz * (Pa) is preferably 0.80 or more, more preferably 2.0 or more, and even more preferably 4.0 or more. * When the content is within the above range, the CNTs are sufficiently disintegrated, and a uniformly dispersed CNT dispersion liquid can be obtained, resulting in high composite adhesion and excellent battery performance. In addition, the complex elastic modulus G * (Pa) is preferably 100.0 or less, more preferably 50.0 or less, and even more preferably 10.0 or less. When the complex elastic modulus G* is within the above range, a CNT dispersion liquid in which the CNTs are stably dispersed without aggregation or precipitation of the CNTs can be obtained, and excellent battery performance can be obtained.
[0109] The degree of CNT disintegration in the CNT dispersion can also be evaluated by the filtration rate of the CNT dispersion. More specifically, the CNT dispersion can be evaluated by measuring the time it takes for the entire amount to pass through when the CNT dispersion is diluted 3 times with a non-aqueous dispersion medium and filtered under reduced pressure. This is thought to be because, when a small amount of aggregates derived from CNTs or other resin components are present in the CNT dispersion, the aggregates cannot pass through the filtration filter or the filtration rate becomes slow. In addition, when the dispersion state of the CNT dispersion is unstable, dispersion shock is likely to occur when the CNT dispersion is diluted with a non-aqueous dispersion medium, and the aggregates are significantly confirmed, so similarly, the CNT dispersion cannot pass through the filtration filter or the filtration rate becomes slow. For the above reasons, the filtration rate can be used as an index for evaluating the dispersion state and dispersion stability of CNTs in a CNT dispersion, and the fluidity of the CNT dispersion. More specifically, it can be measured by the method described in the Examples.
[0110] The fluidity and dispersion stability of the CNT dispersion can be evaluated by checking the acid stability. More specifically, an acid is added to the CNT dispersion, and the initial viscosity of the CNT dispersion containing the acid and the viscosity after the CNT dispersion containing the acid are stored at 40°C for 7 days are measured, and the fluidity and dispersion stability of the CNT dispersion can be evaluated based on the rate of change in viscosity after storage at 40°C for 7 days relative to the initial viscosity. If the CNTs are stably dispersed, the dispersion of the CNTs does not collapse even when acid is added to the CNT dispersion, and good viscosity is maintained over time. On the other hand, even if the CNTs at the initial stage appear to be in a good dispersion state, if the dispersion of the CNTs is not sufficient, the CNTs that do not adsorb the dispersant will aggregate when acid is added, causing poor dispersion, and the CNT dispersion will thicken over time. By evaluating under these conditions, the dispersion state and dispersion stability of the CNTs in the CNT dispersion can be evaluated, taking into account changes over time. More specifically, the measurement can be performed by the method described in the Examples.
[0111] The average fiber length of the CNTs in the CNT dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the CNTs in the CNT dispersion is calculated by observing a sample obtained by diluting the CNT dispersion 50 times with a non-aqueous dispersion medium such as NMP, dropping it onto a substrate, and drying the sample, and then selecting 300 CNTs in the observation photograph, measuring the fiber length of each of them, and averaging them. Here, when the dispersion state of the CNTs is unstable, the dispersion shock is likely to occur by diluting the CNT dispersion with a non-aqueous dispersion medium, and the average fiber length tends to become smaller due to the formation of aggregates. For the above reasons, the dispersion stability can be evaluated by the average fiber length of the CNTs in the CNT dispersion.
[0112] The content of CNT in the CNT dispersion is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the total amount of the CNT dispersion. Also, it is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 8% by mass or less. By keeping it within the above range, the CNT can be present well and stably. It is more preferably 0.1% by mass or more and 20% by mass or less, and even more preferably 0.5% by mass or more and 10% by mass or less.
[0113] In the CNT dispersion, the mass ratio of the dispersant to the CNT (dispersant / CNT) is preferably 0.01 or more, more preferably 0.05 or more, and even more preferably 0.1 or more. Also, it is preferably 1.5 or less, more preferably 1 or less, even more preferably 0.5 or less, and particularly preferably 0.40 or less. By keeping it in the above range, the dispersion stability of the CNT can be further improved. It is more preferably 0.01 or more and 1.5 or less, and even more preferably 0.1 or more and 1 or less.
[0114] The Zr content in the CNT dispersion is preferably 0.01 ppm or more, more preferably 0.1 ppm or more, and even more preferably 1 ppm or more. Also, it is preferably 300 ppm or less, more preferably 150 ppm or less, even more preferably 100 ppm or less, and particularly preferably 50 ppm or less. By setting it in the above range, the dispersion stability of the CNT in the CNT dispersion can be further improved. More preferably, it is 0.01 ppm or more and 300 ppm or less, and even more preferably, it is 0.1 ppm or more and 100 ppm or less.
[0115] The CNT in the CNT dispersion functions as a conductive material. The CNT dispersion may contain a conductive material other than CNT. Examples of other conductive materials include carbon materials such as carbon black, graphene, multilayer graphene, and graphite. When using a conductive material other than CNT, carbon black is preferred from the viewpoint of the adsorption performance of the dispersant, and examples of the carbon black include acetylene black, furnace black, and ketjen black. These carbon blacks may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black.
[0116] The CNT dispersion may be prepared by separately preparing two or more types of CNTs having different average outer diameters and adding them to a dispersion medium. When two or more types of CNTs having different average outer diameters are used as the CNTs, the average outer diameter of the first CNT is preferably 0.5 nm or more and less than 5 nm. The average outer diameter of the second CNT is preferably 1 nm or more and 20 nm or less. For example, the first CNT may be a single-walled CNT, and the second CNT may be a multi-walled CNT. When two or more types of CNTs having different average outer diameters are used as the CNTs, the mass ratio of the first CNT to the second CNT is preferably 1:50 to 50:1, more preferably 1:10 to 10:1, and even more preferably 1:5 to 5:1. By setting the mass ratio of the first CNT to the second CNT within the above range, entanglement between the CNTs is suppressed, and a dispersion with excellent fluidity is obtained.
[0117] <<Carbon nanotube resin composition>> The carbon nanotube resin composition of the present embodiment may contain the carbon nanotube dispersion and a binder resin. The details of the carbon nanotube dispersion are as described above. That is, the carbon nanotube resin composition may contain carbon nanotubes, a dispersant, a non-aqueous dispersion medium, and a binder resin. The carbon nanotube resin composition may further contain an optional component. The details are as described above. The carbon nanotube resin composition can be used as a resin composition for a secondary battery.
[0118] The binder resin is not particularly limited as long as it is normally used as a binder resin for paints, and can be appropriately selected according to the purpose. The binder resin may be a resin that bonds between substances such as active materials, CNTs, and other conductive materials. Examples of the binder resin include homopolymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, and the like as constituent units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose resins such as carboxymethylcellulose or salts thereof; elastomers such as hydrogenated or non-hydrogenated styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies of these resins and copolymers of these resins may also be used. The binder resin may be used alone or in combination of two or more. Among these, when used as a binder resin for the positive electrode of a secondary battery, homopolymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, polytetrafluoroethylene, and modified products and copolymers thereof, are preferred from the viewpoint of durability. When used as a binder resin for the negative electrode of a secondary battery, CMC (carboxymethylcellulose or its salt), hydrogenated or non-hydrogenated styrene-butadiene rubber, polyacrylic acid, and the like, which have good adhesion, are preferred.
[0119] In the CNT resin composition, the binder resin is preferably 0.5 to 30 mass %, and more preferably 0.5 to 25 mass %, based on the total amount of non-volatile content of the CNT resin composition.
[0120] The CNT resin composition is preferably obtained by adding a binder resin to a CNT dispersion liquid and mixing. The binder resin may be used in a solution (varnish) state in which the binder resin is dispersed or dissolved in a dispersion medium or the like, but is preferably used in a state in which it does not contain a dispersion medium, more preferably in a solid state, and particularly preferably in a powder state. By adding a powdered binder resin to a CNT dispersion liquid, the amount of the non-aqueous dispersion medium does not increase when the binder resin is added, so that a CNT resin composition with a high binder resin concentration and non-volatile content concentration can be provided. Here, the form of the binder resin is not particularly limited, and may be, for example, pellet-shaped, powder-shaped, granular, flake-shaped, lump-shaped, chopped fiber, or the like.
[0121] The method of adding the binder resin to the CNT dispersion liquid is not particularly limited, but it is preferable to add the binder resin while stirring the CNT dispersion liquid using a stirring device. The stirring device is not particularly limited, but a disperser (stirring blade) or the like is generally used. There are various types of the stirring device, such as a propeller type and a turbine type, and the shape is not particularly limited as long as it can homogeneously stir the CNT resin composition. In addition, the stirring speed can be appropriately adjusted depending on the size and rotation speed of the stirring blade. The stirring speed is not particularly limited as long as it is within the range allowed in the actual operation process.
[0122] <<Slurry for secondary battery electrode composite material>> The composite slurry of this embodiment may contain the carbon nanotube dispersion, a binder resin, and an active material. The composite slurry of another embodiment may contain the carbon nanotube resin composition and an active material. The details of the carbon nanotube resin composition are as described above. That is, the composite slurry may contain carbon nanotubes, a dispersant, a non-aqueous dispersion medium, a binder resin, and an active material. The composite slurry may further contain an optional component. The details are as described above. The active material may be either a positive electrode active material or a negative electrode active material. The composite slurry can be used as a composite slurry for a secondary battery electrode, and may be either a positive electrode composite slurry for a secondary battery or a negative electrode composite slurry for a secondary battery.
[0123] The composite slurry may contain other optional components as necessary, as long as the object of the present invention is not hindered. The optional components may be added at any timing, such as before preparing the composite slurry, during mixing, after mixing, or a combination of these. The optional components may be those described above in relation to the CNT resin composition.
[0124] The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material may be simply referred to as "active material". The active material is a material that is the basis of the battery reaction, and is roughly classified into a positive electrode active material and a negative electrode active material based on the electromotive force. The composite slurry is preferably in a slurry state in order to improve uniformity and processability.
[0125] <Cathode active material> The positive electrode active material is not particularly limited, but for example, a metal compound such as a metal oxide or metal sulfide capable of reversibly doping or intercalating lithium ions can be used. For example, a lithium manganese composite oxide (e.g., Li x Mn2O4 or LixMnO2), lithium nickel composite oxide (e.g. LixNiO2), lithium cobalt composite oxide (Li x CoO2), lithium nickel cobalt complex oxide (e.g. Li xNi 1-y Co y O2), lithium manganese cobalt composite oxide (e.g., LixMnyCo1-yO2), lithium nickel manganese cobalt composite oxide (e.g., Li x Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxide (e.g., Li x Mn 2-y Ni y O4), etc., composite oxide powders of lithium and transition metals, lithium phosphate powders having an olivine structure (e.g., Li x FePO4, Li x Fe 1-y Mn y PO4, Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxides (e.g., V2O5, V6O 13 ), transition metal oxide powders such as titanium oxide, iron sulfate (Fe2(SO4)3), transition metal sulfide powders such as TiS2 and FeS, etc. However, x, y, z are numbers, 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < y + z < 1. These cathode active materials can also be used alone or in combination of two or more. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to become highly basic due to components derived from raw materials or elution of metal ions, and due to this influence, gelation of the binder resin and deterioration of the dispersion state are likely to occur. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, this embodiment is particularly effective.
[0126] <Negative electrode active material> The negative electrode active material is not particularly limited. For example, metallic Li capable of reversibly doping or intercalating lithium ions, or an alloy thereof, a tin alloy, a silicon alloy negative electrode, Li X TiO2, Li X Fe2O3, Li X Fe3O4, Li XMetal oxide systems such as WO2, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials can be used. However, x is a number and 0 < x < 1. These negative electrode active materials can be used alone or in combination of two or more. In particular, when using a silicon alloy negative electrode, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials, etc.
[0127] The content of CNT in the composite material slurry is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the active material (assuming the mass of the active material is 100% by mass). Also, it is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. If it exceeds the above range, the filling amount of the active material in the electrode will decrease, leading to a decrease in the battery capacity. If it is below the above range, the conductivity of the electrode and the battery may be insufficient.
[0128] The content of the dispersant in the composite material slurry is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, based on the mass of the active material (assuming the mass of the active material is 100% by mass). Also, it is preferably 10% by mass or less, more preferably 5% by mass or less.
[0129] The content of the binder resin in the composite material slurry is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, based on the mass of the active material (assuming the mass of the active material is 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less.
[0130] The non-volatile content in the composite slurry is preferably 40% by mass or more, more preferably 50% by mass or more, based on the mass of the composite slurry (mass of the composite slurry being 100% by mass), and is preferably 90% by mass or less, more preferably 85% by mass or less.
[0131] A preferred method for preparing the composite slurry is to add an active material to the CNT resin composition and stir the mixture. The stirrer used for stirring is not particularly limited. A disperser, homogenizer, etc. can be used as the stirrer.
[0132] The composite slurry may further contain carbon black, and the carbon black functions as a conductive material. The carbon black is preferably contained in the composite slurry within a range that does not impair the effects of the present invention, and the CNT is preferably 1 to 80 mass %, more preferably 1 to 50 mass %, of the total amount of the conductive material including carbon black and CNT. In these ranges, the dispersion state of the CNT can be controlled, and high dispersibility and flowability can be better maintained in a state containing a binder resin. Furthermore, the carbon black is preferably 10 mass % or less, more preferably 5 mass % or less, of the total mass of the composite slurry. The manufacturing method of the composite slurry includes a step of adding an active material to the CNT resin composition, and may further include adding carbon black before, after, simultaneously with, or in a combination of these before and after adding the active material to the CNT resin composition. Alternatively, the active material may be added to a CNT resin composition that already contains carbon black, or the active material and carbon black may be further added to a CNT resin composition that already contains carbon black.
[0133] <<Electrode film>> The electrode film of this embodiment is a coating film formed from the above-mentioned composite slurry. That is, the electrode film may include CNT, a dispersant, a binder resin, and an active material. The active material may be either a positive electrode active material or a negative electrode active material. The electrode film may further include an optional component. Details are as described above. The electrode film can be used as an electrode film for a secondary battery electrode, and may be either an electrode film for a secondary battery positive electrode or an electrode film for a secondary battery negative electrode. The electrode film may be a coating film obtained using the above-mentioned composite slurry, and can be formed, for example, by coating and drying the composite slurry. An electrode can be provided using the electrode film. The electrode may include a current collector and an electrode film. The electrode can be obtained by coating a current collector with a composite slurry and drying it to form a coating film. A positive electrode can be provided by using an electrode film containing a positive electrode active material, and a negative electrode can be provided by using an electrode film containing a negative electrode active material, and these positive and negative electrodes can be provided as the positive and negative electrodes, respectively, of a secondary battery.
[0134] The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.
[0135] The method of applying the composite slurry onto the current collector is not particularly limited, and a known method can be used. Specifically, die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, electrostatic painting, etc. can be mentioned. As a drying method after application, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, etc. can be used, but are not particularly limited thereto. In addition, after application of the composite slurry, a rolling process may be performed using a planographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, preferably 10 μm or more and 300 μm or less.
[0136] <<Secondary battery>> The secondary battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode includes the above-mentioned electrode film. The positive electrode and the negative electrode may each include a current collector and an electrode film. Details are as described above. It is more preferable that the secondary battery is a lithium-ion secondary battery.
[0137] The positive electrode may be prepared by coating a composite slurry containing a positive electrode active material on a current collector and drying the mixture to prepare an electrode film. The negative electrode may be prepared by coating a composite slurry containing a negative electrode active material on a current collector and drying the mixture to prepare an electrode film. The positive electrode active material and the negative electrode active material may be the above-mentioned materials. The composite slurry may be prepared according to the above-mentioned method.
[0138] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous dispersion medium.
[0139] As the electrolyte salt, various conventionally known ones in which ions can move can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be mentioned, but are not limited thereto. It is preferable to dissolve the electrolyte salt in a non-aqueous dispersion medium and use it as an electrolyte solution.
[0140] The non-aqueous dispersion medium is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0141] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.
[0142] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes such as a paper type, a cylindrical type, a button type, a laminated type, etc., depending on the purpose of use. EXAMPLES
[0143] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0144] The following CNTs were used in the examples and comparative examples: BT1003M: LUCAN BT1003M, manufactured by LG Chem Ltd., multi-walled CNT, outer diameter 10-15 nm JENOTUBE10B: Manufactured by JEIO, multilayer CNT, outer diameter 7~12nm
[0145] The following dispersants were used in the examples and comparative examples: H-NBR1: Therban(R)AT 3404 (ARLANXEO, hydrogenated acrylonitrile-butadiene rubber) ·H-NBR2: Zetpole 2000L (manufactured by Zeon Corporation, hydrogenated acrylonitrile-butadiene rubber) ·PVB: BL-10 (manufactured by Sekisui Chemical Co., Ltd., polyvinyl butyral) ·PVP: K-30 (manufactured by ISP, polyvinylpyrrolidone) PVA: Kuraray Poval 3-86SD (Kuraray, modified polyvinyl alcohol)
[0146] In the examples and comparative examples, the following binder resins were used: PVDF: KF Polymer W#7300 (Kureha, polyvinylidene fluoride resin) PTFE: PTFED-210C (Daikin Industries, polytetrafluoroethylene)
[0147] <cnt> Table 1 shows the type of CNT and the manufacturing conditions. The end point index for the dry grinding of the CNTs is a bulk density of 0.045 g / cm. 3 ~0.125g / cm 3 The Zr content is set to be within the range of 3 ppm to 500 ppm.
[0148] (Example 1: CNT1) In a 60 L dynamic mill, zirconia beads with a diameter of 8 mm were charged as the grinding media at a filling rate of 70%, and 100 kg of BT1003M was supplied as the raw CNTs at a flow rate of 120 ± 20 kg / h (hours). The milling was carried out for 2 hours using a circulation grinding method at a peripheral speed of 4 m / s (seconds), yielding CNT1. A sample was taken out and found to have a bulk density of 0.062 g / cm. 3 The Zr content was 6 ppm, and it was confirmed that both the bulk density and Zr content were within the specified range, and the treatment process was terminated. In the treatment process, cooling was performed by running cooling water (10°C) through the vessel (flow rate 10 L / min) so that the powder temperature at the outlet was 45±10°C.
[0149] (Example 2~9: CNT2~9) CNTs 2 to 9 were obtained by dry pulverization of CNTs in the same manner as in Example 1, using the raw CNTs, processing time, processing flow rate, and dry dispersion method listed in Table 1. In each processing step, cooling was performed by running cooling water (10°C) through the vessel (flow rate 10 L / min) so that the outlet powder temperature was 45±10°C.
[0150] (Comparative Example 1: Comparative CNT1) BT1003M in an untreated state without being subjected to crushing treatment was used as comparative CNT1.
[0151] (Comparative Example 2: Comparative CNT2) Using a dynamic mill with a capacity of 60 L, zirconia beads with a diameter of 8 mm were charged as grinding media at a filling rate of 70%. As the raw material CNT, 100 kg of BT1003M was supplied at a flow rate of 120 ± 20 kg / h and processed for 15 hours by a circulating grinding method at a peripheral speed of 4 m / s to obtain Comparative CNT2. During the processing step, cooling water (10°C) was flowed into the vessel (flow rate 10 L / min) to cool it so that the outlet powder temperature would be 45 ± 10°C.
[0152] (Comparative Example 3: Comparative CNT3) Using a dynamic mill with a capacity of 60 L, zirconia beads with a diameter of 8 mm were charged as grinding media at a filling rate of 70%. As the raw material CNT, 100 kg of BT1003M was supplied at a flow rate of 120 ± 20 kg / h and processed for 15 hours by a circulating grinding method at a peripheral speed of 4 m / s to obtain Comparative CNT3. During the grinding process, normal temperature water was flowed into the vessel so that no equipment failure would occur due to temperature rise.
[0153] (Comparative Example 4: Comparative CNT4) Using a ball mill with a capacity of 250 L, zirconia beads with a diameter of 20 mm were charged as grinding media at a filling rate of 35%. As the raw material CNT, 5 kg of BT1003M was charged and processed for 20 hours by a batch grinding method at a peripheral speed of 10 m / s to obtain Comparative CNT4.
[0154] (Comparative Example 5: Comparative CNT5) Using an attrition mill with a capacity of 150 L, zirconia beads with a diameter of 8 mm were charged as grinding media at a filling rate of 70%. As the raw material CNT, 3 kg of BT1003M was charged and processed for 10 hours by a batch grinding method at a rotational speed of 150 min-1 to obtain Comparative CNT5.
[0155] (Physical Properties and Evaluation of CNT) The physical properties of CNT were measured and evaluated by the following method. The results obtained are shown in Table 1.
[0156] (Zr Content) The Zr content of CNT was measured by the following procedure. First, put 0.1 ± 0.02 g of CNT into a decomposition vial, add nitric acid, and decompose it using a microwave sample decomposition device. Add generation to the decomposition solution, adjust the volume to 25 ml, filter it with a membrane filter, and analyze the filtrate using an ICP analyzer to determine the Zr content (ppm).
[0157] <Apparent density X of CNT> The apparent density was measured according to JIS K 5101-12-1 by the following procedure. First, before measurement, pre-treat the CNT by vacuum drying at a pre-treatment temperature of 305 °C for 18 - 21 hours. Next, crush the aggregates formed during the storage of the CNT powder, and prepare a sufficient amount of the sample to freely flow into the measurement container by passing it through a 0.5 mm sieve. Let the prepared CNT powder freely fall into a 30 ml stainless steel cylindrical container, level off the part that bulges above the container surface, then determine the mass of the CNT powder, and divide it by the volume of the container to obtain the apparent density (g / cm 3 ³).
[0158] <Maximum solvent absorption capacity Y of CNT> The maximum solvent absorption capacity Y is the maximum mass of the solvent absorbed per unit mass of CNT when the CNT absorbs the solvent. The maximum mass of the solvent absorbed by the CNT is the total mass of the solvent dropped until just before the solvent starts to flow out from the CNT powder when the solvent is dropped onto the CNT powder. The maximum solvent absorption capacity Y was measured by the following procedure. First, before measurement, pre-treat the CNT by vacuum drying at a pre-treatment temperature of 305 °C for 18 - 21 hours. Then, in a 25 °C environment, put 5 g (V(g)) of CNT powder into a cylindrical polypropylene container with a diameter of 10 cm by natural dropping, and while standing still, drop N-methyl-2-pyrrolidone onto the surface of the CNT powder at 0.5 g per time interval of 1 minute, and measure the total mass (W(g)) of the N-methyl-2-pyrrolidone dropped until just before the liquid of N-methyl-2-pyrrolidone starts to flow out without being absorbed by the CNT powder. Calculate the maximum solvent absorption capacity from the following formula (5). Y = W / V ··· Equation (5) (In Equation (5), V is the mass of CNT, and W is the maximum mass of N-methyl-2-pyrrolidone absorbed by CNT when N-methyl-2-pyrrolidone is dropped onto V (g) of CNT in an environment of 25°C.)
[0159] <Powder resistivity of CNT> Using a powder resistivity measuring device (manufactured by Nitto Seiko Analytic Co., Ltd.: Loresta GP Powder Resistivity Measurement System MCP-PD-51), with a sample mass of 0.8 g, and a powder probe unit (four-probe ring electrode, electrode interval 5.0 mm, electrode radius 1.0 mm, sample radius 12.5 mm), the volume resistivity [Ω·cm] of the conductive powder under various pressures was measured with the applied voltage limiter set to 90 V. At a density of 1 g / cm 3 The value of the powder resistivity of CNT was evaluated.
[0160]
Table 1-1
[0161]
Table 1-2
[0162]
Table 1-3
[0163] Also, in Table 1, the bulk density change rate is the value obtained by the following formula from the bulk density X after dry grinding and the bulk density X' before dry grinding, and the powder resistivity change rate is the value obtained by the following formula from the powder resistivity Re after dry grinding and the powder resistivity Re' before dry grinding. Bulk density change rate (%) = (X / X' - 1) × 100 Powder resistivity change rate (%) = (Re / Re' - 1) × 100
[0164] <CNT dispersion liquid> (Example 1-1) According to the materials and compositions shown in Table 2, the materials were added in order to prepare a CNT dispersion liquid as follows. First, NMP was placed in a stainless steel jacketed tank and heated to 50°C. After adding a dispersant (H-NBR1) and an additive (NaOH) while stirring with a disperser, the mixture was stirred for 1 hour to dissolve the dispersant (H-NBR1). Next, 25 parts by mass of CNT was added to 100 parts by mass of CNT (CNT1) while stirring with a disperser, and a square hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON) and batch dispersion was performed at a speed of 8,000 rpm for 5 minutes. The above CNT addition and dispersion process was repeated four times to add the entire amount of CNT, and the entire mixture became uniform, and batch dispersion was performed with a high shear mixer until the dispersion particle size was 250 μm or less using a grind gauge with a maximum groove depth of 300 μm. Next, the liquid to be dispersed was supplied from the jacketed tank to a bead mill (SC100, manufactured by Nippon Coke) through a pipe, and dispersion was performed by circulation type dispersion with a residence time of 5 minutes under the conditions of bead diameter 1.25 mm, bead filling rate 60%, peripheral speed 10 m / s, and supply speed 800 g / min. Furthermore, the pipe was switched and the liquid to be dispersed was supplied to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine), and a circulation type dispersion process was performed. The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. After dispersing until the viscosity of the liquid to be dispersed at 60 rpm measured with a B-type viscometer (manufactured by TOKI SANGYO, VISCOMETER, MODEL: BL) was 3,000 mPa·s or less, the liquid was processed with 15 passes through the high-pressure homogenizer to obtain CNT dispersion 1.
[0165] (Examples 1-2 to 1-14) Except for changing the materials and compositions according to Table 2, the same procedures as in Example 1-1 were carried out to obtain CNT dispersions 2 to 13.
[0166] (Example 1-15) According to the materials and compositions shown in Table 2, the materials were added in order to prepare a CNT dispersion liquid as follows. First, NMP was placed in a stainless-steel jacketed tank and heated to 50°C. While stirring with a disper, a dispersant (H-NBR1) and an additive (NaOH) were added, and then stirred for 1 hour to dissolve the dispersant (H-NBR1). Subsequently, while stirring with a disper, 25 parts by mass of CNT was added to 100 parts by mass of CNT (CNT1), a square-hole high-shear screen was attached to a high-shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,000 rpm for 5 minutes. By repeating the above CNT addition and dispersion steps 4 times, the total amount of CNT was added, and when the whole became uniform, batch dispersion was performed with a high-shear mixer until the dispersion particle size became 250 μm or less using a grind gauge with a maximum groove depth of 300 μm. Subsequently, the dispersion liquid was supplied from the jacketed tank to a bead mill (SC100, manufactured by Nippon Coke) through a pipe, and circulated dispersion was performed for 10 minutes under the conditions of a bead diameter of 1.25 mm, a bead filling rate of 60%, a peripheral speed of 10 m / s, and a supply speed of 800 g / min. Further, the pipe was switched and the dispersion liquid was supplied to a high-pressure homogenizer (Starburst Turbo HJP-17007, manufactured by Sugino Machine), and circulated dispersion treatment was performed. The dispersion treatment was performed using a single-nozzle chamber at a nozzle diameter of 0.25 mm and a pressure of 100 MPa. After dispersion until the viscosity at 60 rpm measured with a B-type viscometer (VISCOMETER, MODEL: BL, manufactured by TOKI SANGYO) of the dispersion liquid became 3,000 mPa·s or less, treatment was performed 15 times with a high-pressure homogenizer to obtain CNT dispersion liquid 15.
[0167] (Comparative Examples 1-1 to 1-5) Except for changing according to the materials and compositions shown in Table 2, comparative CNT dispersion liquids 1 to 5 were obtained in the same manner as in Example 1-1.
[0168] The additives and acids described in Table 2 are as follows. · NaOH: Sodium hydroxide (manufactured by Tokyo Chemical Industry, purity > 98.0%, granular) · Aminoethanol: 2-Aminoethanol (manufactured by Tokyo Chemical Industry, purity > 99.0%)
[0169] <<Measurement and Evaluation of Physical Property Values of CNT Dispersion Liquid>> The physical properties of the CNT dispersion were measured and evaluated by the following methods. The results are shown in Tables 2 and 3.
[0170] (Shear viscosity of CNT dispersion) Shear rate of CNT dispersion: 1.0 s -1 The viscosity was measured at 25°C with a shear rate of 0.01 to 1000 S using a rheometer (RheoStressl rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a diameter of 60 mm and a 2° cone. -1 The shear rate over time was evaluated by performing the above-mentioned flow curve measurement on the CNT dispersion liquid in a stationary state with the liquid temperature adjusted to 25°C.
[0171] (Complex modulus of CNT dispersion) The complex modulus of the CNT dispersion was evaluated by performing dynamic viscoelasticity measurements at 25°C, a frequency of 1 Hz, and a strain rate range of 0.01% to 5% using a rheometer (RheoStressl rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone of 60 mm diameter and 2°. The shear rate over time was evaluated by performing the above dynamic viscoelasticity measurements on the CNT dispersion in a stationary state with the liquid temperature adjusted to 25°C.
[0172] Table 3 shows the measurement results of the shear viscosity η (Pa·s) and the complex modulus G* (Pa) measured using the CNT dispersions of Examples 1-2, 1-8, and Comparative Example 1-3.
[0173] Table 4 shows the coefficient of determination R obtained by calculating a regression line expressed by the least squares method from a scatter diagram in which the natural logarithm (ln(η)) of the shear viscosity η (Pa s) and the complex elastic modulus G* (Pa) measured in Examples 1-2, 1-8, and Comparative Example 1-3 are plotted. 2 , slope a, and y-intercept b are recorded.
[0174] FIG. 1 shows an example of a scatter diagram in which the results of measurements of the CNT dispersions of Examples 1-2, 1-8, and Comparative Example 1-3 after static storage at 40° C. for 1 day, 7 days, and 14 days are plotted. For example, the coefficient of determination R obtained from the regression line for the CNT dispersion in Example 1-2 2 is 1.00, the slope a is 8.4, the y-intercept b is 4.1, and the coefficient of determination R obtained from the regression line for the CNT dispersion of Comparative Example 1-3 is 2 was 0.79, the slope a was 20.8, and the y-intercept b was -0.5.
[0175] The criteria for judgment in Table 4 are as follows: [Determination coefficient R 2 Criteria for determining A: 0.95 or higher B: 0.90 or more and less than 0.95 C: 0.85 or more and less than 0.90 D: Less than 0.85 [Criteria for slope a] A: 7 to 14 B: 5 or more but less than 7, or 14 or more but less than 15 C: 2 or more but less than 5, or 15 or more but less than 20 D: Less than 2 or 20 or more [Criteria for y-intercept b] A: 0 or more and less than 6 B: -3 or more and less than 0, or 6 or more and less than 8 C: -5 or more but less than -3, or 8 or more but less than 10 D: Less than -5 or 10 or more
[0176] (filtration speed) The dispersibility of the CNT dispersion was evaluated by the filtration rate. The filtration speed test was carried out by adding 80g of NMP to 40g of CNT dispersion and mixing thoroughly by shaking. The entire amount was placed in a 300mL vacuum filtration filter holder, and a scale was placed under the receiving container in the suction filter to measure the weight versus the time it took to pass through a 10μm mesh. The shorter the time it took to filter the entire amount of diluted CNT dispersion, the better the dispersibility. Also, poorly dispersed CNTs were present and the entire amount could not be filtered. If the evaluation criterion was + or higher, it was possible to use it. [Evaluation Criteria] +++: Less than 30 seconds ++: 30 seconds or more and less than 100 seconds +: 100 seconds or more NG: Cannot filter the entire amount
[0177] (acid stability) The fluidity and dispersion stability of the CNT dispersion were evaluated by its acid stability. To evaluate the acid stability, 5 parts by mass of succinic acid (succinic acid: Fujifilm Wako Pure Chemical Industries, purity >99.5%) was added to 100 parts by mass of the CNT dispersion, and the initial viscosity of the CNT dispersion containing acid and the viscosity after storing the CNT dispersion containing acid at 40°C for 7 days were measured, and the rate of change in viscosity after storing at 40°C for 7 days relative to the initial viscosity was calculated and evaluated. The rate of change in viscosity is expressed as a percentage by dividing the viscosity value after storing at 40°C for 7 days by the initial viscosity value. The viscosity of the CNT dispersion was measured using a Brookfield viscometer ("BL" manufactured by Toki Sangyo) at a temperature of 25°C, immediately after thoroughly stirring with a spatula, with the rotor rotating at 60 rpm. The smaller the rate of change, the better, and an evaluation criterion of + or higher indicates practical use. [Evaluation Criteria] +++: Less than 200% ++: 200% or more but less than 500% +: 500% or more but less than 1000% NG: 1000% or more (gelled)
[0178] [Table 2]
[0179] [Table 3]
[0180] [Table 4-1]
[0181] [Table 4-2]
[0182] [Table 4-3]
[0183] <Preparation of carbon nanotube resin composition, positive electrode mixture slurry, and positive electrode> (Examples 2-1 to 2-19, Comparative Examples 2-1 to 2-5) According to the combinations and composition ratios shown in Table 5, carbon nanotube resin compositions, positive electrode mixture slurries, and positive electrodes were prepared as follows. The CNT dispersion was placed in a stainless steel jacketed tank, and the temperature of the jacketed tank was heated to 60°C so that the liquid temperature measured with a thermocouple thermometer reached 60°C. The binder resin was added in its entirety at a rate of 0.8 parts by mass / min while stirring with a disperser. The temperature was adjusted to maintain the liquid temperature of 60°C measured with a thermocouple thermometer, and the binder resin was completely dissolved by stirring with a disperser for 3 hours, to obtain a carbon nanotube resin composition.
[0184] Capacity 150cm 3 The CNT resin composition and the positive electrode active material were added to the plastic container and stirred at 2,000 rpm for 5 minutes using a centrifugal mixer (Thinky, Awatori Rentaro, ARE-310) to obtain a positive electrode mixture slurry. The non-volatile content of the positive electrode mixture slurry was 78 mass%.
[0185] The positive electrode composite slurry was applied onto an aluminum foil having a thickness of 20 μm using an applicator, and then heated and dried in an electric oven at 120±5° C. for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (3 ton hydraulic roll press, manufactured by Sun Metals) to obtain positive electrodes (positive electrodes 1 to 18, comparative positive electrodes 1 to 4). The weight per unit area of the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling is 3.2 g / cm 3 It was.
[0186] In the examples and comparative examples, the following positive electrode active materials were used. NMC1: CellSeed NMC (LiNi 0.6 Co 0.2 Mn 0.2 O2, manufactured by Nippon Chemical Industry Co., Ltd. ·NMC2:S800(LiNi 0.8 Mn 0.1 Co 0.1 O2, made by Kinwa) NCA: NAT-7050 (LiNi 0.8 Co 0.15 Al 0.05 O2, manufactured by BASF Toda Battery Materials) LFP: HED(TM) LFP-400 (lithium iron phosphate, manufactured by BASF)
[0187] <Evaluation of the positive electrode> (Positive electrode conductivity) The surface resistivity (Ω / □) of the composite layer of the obtained positive electrode was measured using Mitsubishi Chemical Analytech's Loresta GP, MCP-T610. After measurement, the thickness of the composite layer was multiplied to obtain the volume resistivity (Ω·cm) of the positive electrode. The thickness of the composite layer was measured at three points in the electrode using a film thickness meter (NIKON, DIGIMICRO MH-15M), and the thickness of the aluminum foil was subtracted from the average value to obtain the volume resistivity (Ω·cm) of the positive electrode. The smaller the volume resistivity, the more desirable it is. [Evaluation Criteria] ++++: Less than 10 Ω cm +++: 10 Ω·cm or more and less than 20 Ω·cm ++: 20Ω·cm or more and less than 30Ω·cm +:30Ω·cm or more
[0188] (Adhesion of positive electrode) The obtained positive electrode was cut into two rectangles of 90 mm x 20 mm with the coating direction as the long axis. A tabletop tensile tester (Strograph E3, manufactured by Toyo Seiki Seisakusho) was used to measure the peel strength, and it was evaluated by a 180-degree peel test method. Specifically, a double-sided tape (No. 5000NS, manufactured by Nitto) of 100 mm x 30 mm size was attached to a stainless steel plate, and the composite layer side of the prepared positive electrode was attached to the other side of the double-sided tape to prepare a test sample. Next, the test sample was fixed vertically so that the short sides of the rectangle were at the top and bottom, and the end of the aluminum foil was peeled off while pulling it from the bottom to the top at a constant speed (50 mm / min), and the average value of the stress at this time was taken as the peel strength. The higher the peel strength, the more desirable it is. [Evaluation Criteria] ++++:0.8N / cm or more +++: 0.5N / cm or more and less than 0.8N / cm ++: 0.3N / cm or more and less than 0.5N / cm +: Less than 0.3N / cm
[0189] [Table 5]
[0190] <Preparation of secondary battery> (Preparation of standard negative electrode) 0.5 parts of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka), 1 part of MAC500LC (carboxymethylcellulose sodium salt Sunrose special type MAC500L, manufactured by Nippon Paper Industries, non-volatile content 100%), and 98.4 parts of water were added to a 150 ml plastic container, and the mixture was stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). 97 parts by mass of artificial graphite (CGB-20, manufactured by Nippon Graphite Industries) was then added as an active material, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). Next, 3.1 parts of SBR (styrene butadiene rubber, TRD2001, non-volatile content 48%, manufactured by JSR) was added and stirred at 2,000 rpm for 30 seconds using a centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain a standard negative electrode composite slurry. The non-volatile content of the standard negative electrode composite slurry was set to 50 mass%.
[0191] The above standard negative electrode composite slurry was applied to a 20 μm thick copper foil current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to obtain a coating weight per unit area of the electrode of 10 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metal, 3 ton hydraulic roll press) to adjust the density of the composite layer to 1.6 g / cm. 3 A standard negative electrode was prepared.
[0192] (Examples 3-1 to 3-19, Comparative Examples 3-1 to 3-5) The positive and negative electrodes shown in Table 8 were punched out to 50 mm x 45 mm and 45 mm x 40 mm, respectively, and the punched positive and negative electrodes and the separator (porous polypropylene film) inserted between them were inserted into an aluminum laminate bag and dried in an electric oven at 70 ° C. for 1 hour. Then, in a glove box filled with argon gas, 2 mL of electrolyte (a non-aqueous electrolyte in which ethylene carbonate, dimethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1, and 1 part by mass of vinylene carbonate was added to 100 parts by mass as an additive, and LiPF6 was dissolved at a concentration of 1 M) was injected, and the aluminum laminate was sealed to prepare secondary batteries.
[0193] <Battery evaluation> (Rate characteristics of secondary batteries) The obtained secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cutoff current 1mA (0.02C)) at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, constant current discharging was performed at a discharge current of 10mA (0.2C) and a discharge end voltage of 3V. After repeating this operation three times, constant current / constant voltage charging (cutoff current (1mA0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, and constant current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage reached 3.0V, and the discharge capacity was calculated for each. The rate characteristic can be expressed as the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic=3C discharge capacity / third 0.2C discharge capacity×100(%) The higher the rate characteristic, the more desirable it is. [Evaluation Criteria] ++++:80% or more +++: 60% or more but less than 80% ++: 40% or more but less than 60% +: Less than 40%
[0194] (Cycle characteristics of secondary batteries) The obtained secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cutoff current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 200 times. The cycle characteristics can be expressed as the ratio of the 3rd 0.5C discharge capacity at 25°C to the 200th 0.5C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristic=200th 0.5C discharge capacity / 3rd 0.5C discharge capacity×100(%) The higher the cycle characteristic, the more desirable it is. [Evaluation Criteria] ++++:85% or more +++: 80% or more but less than 85% ++: 50% or more but less than 80% +: Less than 50%
[0195] [Table 6]
[0196] As shown in Tables 2 to 6, it was confirmed that the carbon nanotubes satisfying the scope of the present invention exhibited excellent conductivity and dispersibility, and the carbon nanotube dispersion liquid containing the carbon nanotubes had excellent fluidity and high dispersion stability and storage stability. In addition, the secondary battery electrode composite slurry had excellent CNT dispersibility in a state containing an active material, and the electrode film using the same had high conductivity and adhesion. Furthermore, the obtained secondary battery had excellent rate characteristics and cycle characteristics. This confirmed that the secondary battery had high output, high capacity, and long life. CNT2 to 4 in Examples 2 to 4 and CNT6 to 9 in Examples 6 to 9 each satisfy the range of the present invention, and the CNT dispersions using these exhibited excellent filterability and acid stability, and the battery performance of secondary batteries using these was improved. CNT1 in Example 1 and CNT5 in Example 5 are reference examples.
[0197] Although the present invention has been described above with reference to the embodiment, the present invention is not limited to the above. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the invention.< / cnt>
Claims
1. Bulk density X is 0.095 g / cm 3 0.125g / cm or more 3 The carbon nanotube has a Zr content of 5 ppm or more and 500 ppm or less, and a maximum solvent absorption capacity Y of the carbon nanotube defined by the following formula (5) of 8.0 or more. Y=W / V Equation (5) (In formula (5), V is the mass (g) of the carbon nanotube, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotube when N-methyl-2-pyrrolidone is dropped onto a carbon nanotube of V (g) in a 25° C. environment.)
2. Bulk density X (g / cm 3 2. The carbon nanotube according to claim 1, wherein the maximum solvent absorption capacity Y of the carbon nanotube satisfies all of the following formulas (1) to (4): Y≦-200X+37...Formula (1) Y≧200X-17...Formula (2) Y≧-200X+27...Formula (3) Y≦200X+7...Formula (4)
3. 3. The carbon nanotube according to claim 1, wherein the average fiber length is from 0.2 μm to 1.1 μm.
4. 3. The carbon nanotube according to claim 1, having an average fiber length of 0.2 μm or more and 1.0 μm or less, and a Zr content of 15 ppm or more and 200 ppm or less.
5. A carbon nanotube dispersion comprising the carbon nanotubes according to claim 1 or 2, a dispersant, and a non-aqueous dispersion medium.
6. The coefficient of determination R of the regression line represented by the following formula (I) 2 6. The carbon nanotube dispersion liquid according to claim 5, wherein the y-intercept b is −5≦b<10, and the y-intercept a is 2≦a<20. y=ax+b...Formula (I) (Equation (1) is a regression line obtained by the least squares method from a scatter diagram plotting x on the horizontal axis and y on the vertical axis, the scatter diagram being obtained by measuring carbon nanotube dispersions each having a static storage temperature and number of days of 40° C. for 1 day, 40° C. for 7 days, and 40° C. for 14 days, respectively, The number of days elapsed by static storage is i, the static storage temperature is 40° C., and the shear rate is 1.0 s -1 The shear viscosity at η i (Pa s), the complex modulus of elasticity at 25 ° C. and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is G * i When (Pa) is used, x is 25° C., shear rate 1.0 s -1 The shear viscosity η i (Pa s) natural logarithm (ln(η i )), y is the complex elastic modulus G at 25 ° C. and a frequency of 1 Hz * i (Pa), i is 1, 7, and 14, with the production date of the carbon nanotube dispersion being day 0.
7. A carbon nanotube resin composition comprising the carbon nanotube dispersion according to claim 5 and a binder resin.
8. A composite slurry comprising the carbon nanotube dispersion liquid according to claim 5, a binder resin, and an active material.
9. An electrode film formed from the composite slurry according to claim 8.
10. A secondary battery comprising a positive electrode and a negative electrode, at least one of the positive electrode and the negative electrode having the electrode film according to claim 9.
11. The method includes a step of dry-pulverizing the carbon nanotubes using a milling device including a grinding medium made of a metal or ceramic material, the dry-pulverization being a pass-type grinding or a circulation-type grinding, and the carbon nanotubes after the dry-pulverization have a bulk density X of 0.095 g / cm 3 0.125g / cm or more 3 The present invention relates to a method for producing carbon nanotubes, the method comprising the steps of: a Zr content of 5 ppm or more and 500 ppm or less; and a maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) of 8.0 or more. Y=W / V Equation (5) (In formula (5), V is the mass (g) of the carbon nanotube, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotube when N-methyl-2-pyrrolidone is dropped onto a carbon nanotube of V (g) in a 25° C. environment.)
12. The method for producing carbon nanotubes according to claim 11, wherein a rate of change between the bulk density X after dry-pulverization and the bulk density X' before dry-pulverization is -60% or more and 1000% or less. Bulk density change rate (%) = (X / X'-1) x 100
13. The method for producing carbon nanotubes according to claim 11, wherein a rate of change between powder resistivity Re after dry-pulverization and powder resistivity Re' before dry-pulverization is 1% or more and 20% or less. Powder resistance change rate (%)=(Re / Re′−1)×100
14. The method for producing carbon nanotubes according to claim 11, wherein the grinding media is zirconia beads, and the diameter of the zirconia beads is more than 5 mm and less than 10 mm.
15. The method for producing carbon nanotubes according to claim 11, wherein the carbon nanotubes after the dry pulverization have an average fiber length of 0.2 μm or more and 1.1 μm or less.
16. The method for producing carbon nanotubes according to claim 11, wherein the carbon nanotubes after the dry milling have an average fiber length of 0.2 μm or more and 1.0 μm or less and a Zr content of 15 ppm or more and 200 ppm or less.
17. A method for producing a carbon nanotube dispersion liquid, comprising the steps of mixing and dispersing the carbon nanotubes according to any one of claims 11 to 16, a dispersant, and a non-aqueous dispersion medium.
Citation Information
Patent Citations
Carbon nanotube, carbon nanotube dispersion, and utilization thereof
JP2020029372A
Conductive material dispersion, binder resin-containing conductive material dispersion, slurry for electrode film, electrode film, and non-aqueous electrolyte secondary battery
JP2022042689A
Conductive material dispersion, binder resin-containing conductive material dispersion, slurry for electrode film, electrode film, and non-aqueous electrolyte secondary battery
JP2022042691A
Carbon nanotube dispersion with improved processability and preparation method thereof
KR102125933B1
Cited By
Semiconductor device
CN122458817A
Semiconductor device
DE102026102418A1